Resin composition, cured product of resin composition, resin sheet, printed wiring board, flexible substrate, and semiconductor device
By adding a polymer containing a butadiene skeleton, an inorganic filler material and an allylbenzooxazine compound to the resin composition, the problems of low heat resistance and moisture resistance of the cured products of the existing resin composition are solved, and higher heat resistance and moisture resistance are achieved.
Patent Information
- Application Number
- CN202011270935.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-20
- Filing Date
- 2020-11-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-11-13
AI Technical Summary
The conventional resin composition containing a butadiene skeleton and an inorganic filler material have low heat resistance and moisture resistance.
A resin composition containing a polymer containing a butadiene skeleton, an inorganic filler material and an allyl group-containing benzooxazine compound is used, and the content of the inorganic filler material is 60% by mass or less.
The heat resistance and moisture resistance of the cured product of the resin composition are significantly improved, and are suitable for flexible substrates, printed wiring boards and semiconductor devices.
Smart Images

Figure BDA0002777675110000021 
Figure BDA0002777675110000041 
Figure BDA0002777675110000042
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and further to a cured product of the resin composition, and a resin sheet, a printed wiring board, a flexible substrate, and a semiconductor device obtained by using the resin composition. Background Art
[0002] It is known that a semiconductor device including a thin and lightweight flexible substrate as a printed wiring board. A flexible substrate generally refers to a printed wiring board (FPC) having a bendable flexibility, and depending on the circumstances, sometimes refers to a circuit board on which components are further assembled on the printed wiring board. For a printed wiring board, there is a printed wiring board comprising an insulating layer formed by a cured product of a resin composition. By forming the insulating layer of a printed wiring board using a cured product of a resin composition, thinning and lightweighting can be achieved.
[0003] As a resin composition for forming an insulating layer of a printed wiring board, for example, Patent Document 1 discloses a bismaleimide resin composition.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: Japanese Patent Application Publication No. 2016-074871. Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, when using a resin composition containing a polymer containing a butadiene skeleton and an inorganic filler, the heat resistance and moisture resistance of the cured product of the resin composition are sometimes low. Here, the polymer containing a butadiene skeleton refers to a polymer containing a butadiene skeleton containing a butadiene diyl structure, a polybutadiene structure, etc., which is a material that can be expected to contribute to the flexibility of a flexible substrate. It should be noted that for a flexible substrate, the above-mentioned issues (technical problems) are significantly generated, but are not limited to flexible substrates, and the above-mentioned issues may also be generated for a rigid substrate.
[0009] Therefore, there is a demand for a resin composition that can provide a cured product having excellent heat resistance and moisture resistance.
[0010] The object of the present invention is to provide a resin composition that can produce a cured product having excellent heat resistance and moisture resistance; a cured product of the resin composition; a resin sheet comprising the resin composition; a printed wiring board or a flexible substrate comprising an insulating layer formed using the cured product of the resin composition, and a semiconductor device.
[0011] Means for solving problems
[0012] The present inventors have conducted intensive research and have found that a resin composition can solve the above-mentioned problems, thereby completing the present invention. The resin composition is a resin composition comprising (A) a polymer containing a butadiene skeleton, (B) an inorganic filler, and (C) a benzoxazine compound containing a substituted or unsubstituted allyl group, wherein when the non-volatile component in the resin composition is set to 100% by mass, the content of the inorganic filler (B) is 60% by mass or less and greater than 0% by mass.
[0013] That is, the present invention includes the following contents:
[0014] [1] A resin composition comprising (A) a polymer containing a butadiene skeleton, (B) an inorganic filler, and (C) a benzoxazine compound containing a substituted or unsubstituted allyl group, wherein the content of the inorganic filler (B) is 60% by mass or less and greater than 0% by mass, based on 100% by mass of a non-volatile component in the resin composition;
[0015] [2] The resin composition according to [1], wherein the component (A) is a polymer having a butadiene skeleton and containing one or more aromatic groups in the molecule;
[0016] [3] The resin composition according to [2], wherein at least one of the aromatic groups constitutes a part of a phenoxy structure;
[0017] [4] The resin composition according to [3], wherein the phenoxy structure comprises a phenoxy structure represented by the following formula (A2-2):
[0018] [Chemical formula 1]
[0019]
[0020] In the above formula (A2-2), A a1 and A a2 is a chemical bond (connecting bond), A a3 ~A a6 Each is independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted linear alkyl group having 1 to 5 carbon atoms;
[0021] [5] The resin composition according to any one of [2] to [4], wherein the component (A) is a butadiene skeleton-containing polymer having one aromatic group between two butadiene skeletons (interposed between two butadiene skeletons);
[0022] [6] The resin composition according to any one of [1] to [5], wherein the content of the component (A) is 15% by mass or more when the non-volatile component in the resin composition is 100% by mass;
[0023] [7] The resin composition according to any one of [1] to [6], wherein the content of the component (A) is 50% by mass or less when the non-volatile component in the resin composition is 100% by mass;
[0024] [8] The resin composition according to any one of [1] to [7], wherein the content of the component (B) is less than 50% by mass when the non-volatile component in the resin composition is 100% by mass;
[0025] [9] The resin composition according to any one of [1] to [8], wherein the content of the component (B) is 10% by mass or more when the non-volatile component in the resin composition is 100% by mass;
[0026]
[10] The resin composition according to any one of [1] to [9], wherein the component (C) is a benzoxazine compound containing two or more benzoxazine structures in the molecule;
[0027]
[11] The resin composition according to any one of [1] to
[10] , wherein the component (C) is a benzoxazine compound containing two or more allyl groups in the molecule;
[0028]
[12] The resin composition according to any one of [1] to
[11] , wherein the content of the component (C) is 0.01% by mass or more when the non-volatile component in the resin composition is 100% by mass;
[0029]
[13] The resin composition according to any one of [1] to
[12] , wherein the water absorption of the cured product is less than 0.2%;
[0030]
[14] The resin composition according to any one of [1] to
[13] , which is used for forming an insulating layer;
[0031]
[15] A cured product, which is a cured product of the resin composition according to any one of [1] to
[14] ;
[0032]
[16] A resin sheet comprising a support and a resin composition layer provided on the support and comprising the resin composition described in any one of [1] to
[14] ;
[0033]
[17] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition described in any one of [1] to
[14] or a cured product described in
[15] ;
[0034]
[18] A flexible substrate comprising an insulating layer formed from a cured product of the resin composition described in any one of [1] to
[14] or a cured product described in
[15] ;
[0035]
[19] A semiconductor device comprising the printed wiring board described in
[17] or the flexible substrate described in
[18] .
[0036] Effects of the Invention
[0037] According to the present invention, there can be provided: a resin composition that can produce a cured product having excellent heat resistance and moisture resistance; a cured product of the resin composition; a resin sheet comprising the resin composition; a printed wiring board or a flexible substrate comprising an insulating layer formed using the cured product of the resin composition, and a semiconductor device. DETAILED DESCRIPTION
[0038] Hereinafter, the present invention will be described in detail in its preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be arbitrarily modified and implemented without departing from the scope of the claims of the present invention and their equivalents.
[0039] [Resin composition]
[0040] The resin composition of the present invention comprises: (A) a polymer containing a butadiene skeleton (hereinafter also referred to as "Bu polymer"), (B) an inorganic filler and (C) a benzoxazine compound containing a substituted or unsubstituted allyl group, and when the non-volatile component in the resin composition is set to 100% by mass, the content of the inorganic filler (B) is 60% by mass or less and greater than 0% by mass. In order to ensure the flexibility of the cured product, the resin composition of the present invention comprises the component (A), and further comprises specific amounts of the components (B) and (C), so that a cured product with excellent heat resistance and moisture resistance can be obtained.
[0041] The resin composition may further include any component combined with the components (A) to (C). Examples of the arbitrary component include (D) a thermosetting resin (excluding the components (A) and (C), (E) a curing accelerator (excluding the components (A), (C) and (D), and (F) other additives. The components included in the resin composition are described in detail below.
[0042] <(A) Polymer containing a butadiene skeleton (Bu polymer)>
[0043] The resin composition contains a "polymer containing a butadiene skeleton" as component (A). The polymer containing a butadiene skeleton refers to a polymer containing a butadiene skeleton (a1) described later. By including component (A) in the resin composition, it is expected to obtain a flexible cured product and a flexible substrate containing the cured product as an insulating layer. Component (A) can be used alone or in combination of two or more.
[0044] (Butadiene skeleton (a1))
[0045] (A) component contains one or more butadiene skeletons (a1) in the molecule. Butadiene skeleton (a1) refers to a skeleton containing a butenediyl structure. Here, the butenediyl structure is a general term for groups in which the hydrogen atoms contained in cis-2-butene-1,4-diyl, trans-2-butene-1,4-diyl, vinylethylene (i.e., 3-butene-1,2-diyl), and these groups are replaced by other atoms or atomic groups. The number of butenediyl structures contained in the butadiene skeleton (a1) can be one or more. From the viewpoint of obtaining a more flexible cured product, the number of butenediyl structures contained in the butadiene skeleton (a1) is preferably multiple, and the butadiene skeleton (a1) is preferably a polybutadiene structure (hereinafter also referred to as "PBu structure") formed by combining one or more butenediyl structures. Among them, the double bonds contained in a part of the butenediyl structures in the polybutadiene structure can be hydrogenated.
[0046] Examples of the butenediyl structure include structures represented by the following formula (A1-1), the following formula (A1-2), or the following formula (A1-3).
[0047] [Chemical formula 2]
[0048]
[0049] (In the above formula (A1-1), X 1 are each independently a hydrogen atom or a halogen atom).
[0050] [Chemical formula 3]
[0051]
[0052] (In the above formula (A1-2), X 2 are each independently a hydrogen atom or a halogen atom).
[0053] [Chemical formula 4]
[0054]
[0055] (In the above formula (A1-3), X 3 are each independently a hydrogen atom or a halogen atom).
[0056] In the above formula (A1-1), formula (A1-2) and formula (A1-3), as a group X that can be constituted 1 , X 2 , X 3Specific examples of the halogen atom include chlorine atoms, fluorine atoms, etc. In the above formula (A1-1), formula (A1-2) and formula (A1-3), from the viewpoint of obtaining a cured product with excellent dielectric properties, the group X 1 , X 2 , X 3 A hydrogen atom is preferred.
[0057] From the viewpoint of inhibiting the reaction of the double bond sites in the structures represented by the above formulas (A1-1), (A1-2) and (A1-3) with other molecules or other resins, the butadiene skeleton (a1) preferably comprises the structure represented by the above formula (A1-1) or the structure represented by the above formula (A1-2), thereby maintaining the expected flexibility of the cured product.
[0058] The polybutadiene structure (PBu structure) is preferably a polybutadiene structure represented by the following formula (A1). The polybutadiene structure represented by the following formula (A1) at least includes the structure represented by the above formula (A1-1) or the structure represented by the above formula (A1-2). The polybutadiene structure represented by the following formula (A1) may include both the structure represented by the above formula (A1-1) and the structure represented by the above formula (A1-2).
[0059] [Chemical formula 5]
[0060]
[0061] (In the above formula (A1), n is an integer greater than or equal to 2).
[0062] (Aromatic group (a2))
[0063] (A) component is preferably a Bu polymer containing the above-mentioned butadiene skeleton (a1) and one or more aromatic groups (a2) in the molecule. The aromatic group (a2) is preferably a divalent or trivalent aromatic group. For (A) component, an aromatic group (a2) is contained in the molecule close to the butadiene skeleton (a1), thereby obtaining a cured product with excellent heat resistance. By making the number of aromatic groups (a2) contained in (A) component multiple, a cured product with better heat resistance can be obtained. The multiple aromatic groups (a2) contained in one molecule of (A) component may be the same or different.
[0064] Examples of the aromatic group (a2) are divalent or trivalent groups having a structure represented by the following formula (A2-1);
[0065] [Chemical formula 6]
[0066]
[0067] (In the above formula (A2-1), A 1 ~A6 Two or three of them are chemical bonds, and A is not a chemical bond. 1 ~A 6 Each independently represents a hydrogen atom, a halogen atom or a substituted or unsubstituted linear alkyl group having 1 to 5 carbon atoms).
[0068] In the above formula (A2-1), A which can form a non-chemical bond 1 ~A 6 Specific examples of halogen atoms include chlorine atoms and fluorine atoms. 1 ~A 6 Specific examples of the straight-chain alkyl group include a methyl group, an ethyl group, an n-propyl group, an n-butyl group and the like, among which a methyl group is preferred.
[0069] As A in the above formula (A2-1) 1 ~A 6 The substituents that the linear alkyl group may have include, for example, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted aryl group having 6 to 15 carbon atoms, a halogen atom, a sulfonyl group, a cyano group, a nitro group, a mercapto group, and a hydroxyl group. In addition, at least one carbon atom contained in the linear, branched or cyclic alkyl group and the substituted or unsubstituted aryl group having 6 to 15 carbon atoms may be selected from -O-, -S-, -SO- 2 -, -NH-, -CO-, -CONH-, -NHCO-, -CO-O-, and -O-CO- are substituted with heteroatom-containing groups. Specific examples of linear alkyl groups that can constitute substituents include methyl, ethyl, propyl, n-butyl, etc. Specific examples of branched alkyl groups that can constitute substituents include isobutyl, etc. Specific examples of cyclic alkyl groups that can constitute substituents include cyclopentyl, cyclohexyl, etc. Specific examples of aryl groups include phenyl, naphthyl, etc.
[0070] For the first example of the aromatic group (a2), A 1 ~A 6 The two in it are chemical bonds (i.e., divalent groups), and A is not a chemical bond. 1 ~A 6 For the second example of the aromatic group (a2), A 1 ~A 6 Two of them are chemical bonds, and A is not a chemical bond. 1 ~A 6 In the third example of the aromatic group (a2), at least one is a methyl group. 1 ~A 6 The three in it are chemical bonds (i.e., trivalent groups), and the A that is not a chemical bond 1 ~A 6All are hydrogen atoms.
[0071] Among the multiple chemical bonds of the aromatic group (a2), it is preferred that at least one chemical bond is bonded to an oxygen atom. That is, the aromatic group (a2) preferably constitutes a part of the phenoxy structure (a2-1) described later. In one embodiment, the aromatic group (a2) constitutes a part of the phenoxy structure (a2-1) described later.
[0072] The phenoxy structure (a2-1) refers to a divalent group obtained by removing two hydrogen atoms from hydrogen atoms bonded to a carbon atom or an oxygen atom possessed by a substituted or unsubstituted phenol.
[0073] The phenoxy structure (a2-1) preferably includes a divalent phenoxy structure represented by the following formula (A2-2). Since the phenoxy structure is a rigid structure, a cured product having excellent heat resistance can be obtained.
[0074] [Chemical formula 7]
[0075]
[0076] (In the above formula (A2-2), A a1 ~A a6 Two of them are chemical bonds, and the remaining four are each independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted linear alkyl group having 1 to 5 carbon atoms. a1 In the case of non-chemical bonds, it is a hydrogen atom).
[0077] In the above formula (A2-2), A which can form a non-chemical bond a1 ~A a6 Specific examples of halogen atoms include chlorine atoms and fluorine atoms. a1 ~A a6 Specific examples of the straight-chain alkyl group include methyl, ethyl, n-propyl, n-butyl, etc. From the perspective of obtaining a cured product with excellent dielectric properties, A which is not a chemical bond a1 ~A a6 Preferred is a hydrogen atom or a methyl group.
[0078] As A in the above formula (A2-2) a1 ~A a6 The substituents that the linear alkyl group may have include, for example, a substituted or unsubstituted linear, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted aryl group having 6 to 15 carbon atoms, a halogen atom, a sulfonyl group, a cyano group, a nitro group, a mercapto group, and a hydroxyl group. In addition, at least one carbon atom contained in the linear, branched or cyclic alkyl group and the substituted or unsubstituted aryl group having 6 to 15 carbon atoms may be selected from -O-, -S-, -SO- 2-, -NH-, -CO-, -CONH-, -NHCO-, -CO-O-, and -O-CO- are substituted with heteroatom-containing groups. Specific examples of linear alkyl groups that can constitute substituents include methyl, ethyl, propyl, n-butyl, etc. Specific examples of branched alkyl groups that can constitute substituents include isobutyl, etc. Specific examples of cyclic alkyl groups that can constitute substituents include cyclopentyl, cyclohexyl, etc. Specific examples of aryl groups include phenyl, naphthyl, etc.
[0079] In the first example of the phenoxy structure (a2-1), in the above formula (A2-2), A a1 is a hydrogen atom, and in the A that is not a chemical bond a2 ~A a6 In the second example of the phenoxy structure (a2-1), in the above formula (A2-2), A a1 is a chemical bond, and in A which is not a chemical bond a2 ~A a6 In the third example of the phenoxy structure (a2-1), in the above formula (A2-2), A which is not a chemical bond a1 ~A a6 All are hydrogen atoms.
[0080] In one embodiment, the phenoxy structure (a2-1) comprises a phenoxy structure represented by the following formula (A2-3);
[0081] [Chemical formula 8]
[0082]
[0083] (In the above formula (A2-3), A b1 and A b2 is a chemical bond, A b3 ~A b6 Each independently represents a hydrogen atom, a halogen atom or a substituted or unsubstituted linear alkyl group having 1 to 5 carbon atoms).
[0084] In the above formula (A2-3), A which is not a chemical bond b3 ~A b6 Each independently of the A in the above formula (A2-2) which is not a chemical bond a1 ~A a6 The meaning is the same. b3 ~A b6 Among them, at least one is preferably a methyl group.
[0085] The component (A) is preferably a Bu polymer having a plurality of the above-mentioned phenoxy structures (a2-1). The plurality of phenoxy structures (a2-1) contained in one molecule of the component (A) may be the same or different from each other. The component (A) is more preferably a polyphenoxy structure (hereinafter also referred to as a "PPO structure") formed by combining (connecting) the same or different phenoxy structures (a2-1) with each other. By having a plurality of phenoxy structures (a2-1) contained in one molecule of the component (A), a cured product with better heat resistance can be obtained.
[0086] The polyphenyloxy structure (PPO structure) preferably includes at least one skeleton selected from (a2-a) a polyphenylene ether skeleton (hereinafter also referred to as a "PPE skeleton"), (a2-b) a cresol novolac skeleton, and (a2-c) a phenol novolac skeleton. From the viewpoint of obtaining a cured product with better moisture resistance, the polyphenyloxy structure (PPO structure) preferably includes a PPE skeleton. It is believed that the reason for this is that the PPE skeleton tends to have lower polarity than the phenol novolac skeleton and the cresol novolac skeleton, and thus the affinity with water in the obtained cured product is also low, resulting in a cured product with excellent moisture resistance.
[0087] The PPE skeleton (a2-a) is a skeleton containing a structure represented by the following formula (A2-4) as a repeating unit. It is preferred to adjust the average number of PPE skeletons per molecule in the Bu polymer so as to satisfy the range of the weight average molecular weight or the range of the number average molecular weight described below.
[0088] [Chemical formula 9]
[0089]
[0090] (In the above formula (A2-4), A c1 ~A c6 A in the above formula (A2-2) a1 ~A a6 The meaning is the same. c1 is the first chemical bond, A c2 ~A c6 One of them is the second chemical bond).
[0091] In the above formula (A2-4), preferably A c4 It is located in the para position relative to the carbon bonded to the oxygen atom and is the second chemical bond, that is, the PPE skeleton preferably includes a poly-p-phenylene ether skeleton (hereinafter also referred to as "p-PPE skeleton"). The p-PPE skeleton is preferably a p-PPE skeleton including a 2,6-dimethyl-1,4-phenylene ether structure represented by the following formula (A2-4a) in the structure represented by the above formula (A2-4).
[0092] [Chemical formula 10]
[0093]
[0094] (In the above formula (A2-4a), * is a chemical bond).
[0095] The p-PPE skeleton preferably includes a p-PPE skeleton represented by the following formula (1), formula (2), formula (3) or formula (4). As represented by formula (2), formula (3) and formula (4), a plurality of PPE skeletons may be linked to each other via a linking group.
[0096] [Chemical formula 11]
[0097]
[0098] (In formula (1), na represents the number of repeating units, which is an integer greater than or equal to 2).
[0099] [Chemical formula 12]
[0100]
[0101] (In formula (2), nb represents the number of repeating units, which is an integer greater than or equal to 1).
[0102] [Chemical formula 13]
[0103]
[0104] (In formula (3), nc represents the number of repeating units, which are each independently an integer greater than or equal to 1).
[0105] [Chemical formula 14]
[0106]
[0107] (In formula (4), nd represents the number of repeating units, which are each independently an integer greater than or equal to 1).
[0108] The cresol novolac skeleton (a2-b) includes a structure represented by the following formula (A2-5): It is preferred to adjust the average number of cresol novolac skeletons per molecule in the Bu polymer so as to satisfy the range of the weight average molecular weight or the range of the number average molecular weight described below.
[0109] [Chemical formula 15]
[0110]
[0111] (In the above formula (A2-5), A d1 and A d4 is a chemical bond, A d2 and Ad3 R are each independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms. d1 and R d2 Each independently represents a hydrogen atom, a substituted or unsubstituted linear alkyl group having 1 to 10 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms. na2 represents the number of repeating units, which is an integer greater than or equal to 2).
[0112] As R in the above formula (A2-5) d1 and R d2 Examples of the straight-chain alkyl group in include methyl, ethyl, n-propyl, and n-butyl. d1 and R d2 The aryl group in A includes phenyl, benzyl, tolyl, naphthyl and the like. d2 , A d3 , R d1 and R d2 The substituents that the linear alkyl and aryl groups may have are the same as those in the group A b3 ~A b6 The substituents that the linear alkyl group and the aryl group may have are the same.
[0113] In the above formula (A2-5), from the viewpoint of improving the solubility when preparing the resin varnish, R d1 and R d2 are all hydrogen atoms. d1 and R d2 The number of carbon atoms in the linear alkyl group is preferably from 1 to 3, more preferably from 1 to 2, particularly preferably 1.
[0114] The phenol novolac skeleton (a2-c) includes a structure represented by the following formula (A2-6): It is preferred to adjust the average number of phenol novolac skeletons per molecule in the Bu polymer so as to satisfy the range of the weight average molecular weight or the range of the number average molecular weight described below.
[0115] [Chemical formula 16]
[0116]
[0117] (In the above formula (A2-6), A e1 and A e5 is a chemical bond, A e2 ~A e4 are independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms (excluding A e2 ~A e4 (when at least one of R is methyl). e1 and R e2Each independently represents a hydrogen atom, a substituted or unsubstituted linear alkyl group having 1 to 10 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms. na3 represents the number of repeating units, which is an integer greater than or equal to 2).
[0118] As R in the above formula (A2-6) e1 and R e2 Examples of the straight-chain alkyl group in include ethyl, n-propyl, and n-butyl. e1 and R e2 The aryl group in A includes phenyl, naphthyl, etc. e2 ~A e4 , R e1 and R e2 The substituents that the linear alkyl and aryl groups may have are the same as those in the group A b3 ~A b6 The substituents that the linear alkyl group and the aryl group may have are the same.
[0119] In the above formula (A2-6), from the viewpoint of improving the solubility when preparing the resin varnish, R e1 and R e2 Preferably, they are all hydrogen atoms. e1 and R e2 The number of carbon atoms in the linear alkyl group is preferably from 1 to 3, more preferably from 1 to 2, particularly preferably 1.
[0120] For component (A), it is preferred that there is a polymer containing a butadiene skeleton in which one aromatic group (a2) is present between two butadiene skeletons (a1). By having one aromatic group (a2) between two butadiene skeletons (a1), a cured product with better heat resistance can be obtained. It is believed that the reason is that the aromatic group (a2) with higher heat resistance than the butadiene skeleton (a1) is present near the butadiene skeleton (a1). From this viewpoint, the aromatic group (a2) preferably constitutes a part of the above-mentioned phenoxy structure (a2-1), and the phenoxy structure (a2-1) is more preferably a polyphenoxy structure (PPO structure).
[0121] In one embodiment, the Bu polymer is a block copolymer of a "first block comprising a polybutadiene structure (PBu structure)" and a "second block comprising a PPO structure". Such a block copolymer can be produced, for example, by polymerizing a first monomer corresponding to the first block (e.g., "G3000" manufactured by Nippon Soda Co., Ltd., "SA90" manufactured by SABIC Corporation) and a second monomer corresponding to the second block.
[0122] In addition, (A) component is preferably a Bu polymer having one or more connecting groups selected from carbamate bond, ester bond (excluding the ester bond contained in the carbamate bond), amide bond and the imide structure described later between the butadiene skeleton (a1) and the aromatic group (a2). The molecular structure (for example, the chain length of the block containing the butadiene skeleton (a1), the chain length of the block containing the aromatic group (a2)) is controlled by the connecting group, thereby obtaining a cured product with better heat resistance. In a certain embodiment, the Bu polymer is a cresol novolac resin, a phenol novolac resin or a polyphenylene ether resin containing a PBu structure and a PPO structure, and in another embodiment, the Bu polymer is a polyimide resin containing a PBu structure and an imide structure. The imide structure is a structure formed by combining two carbonyl groups on a primary amine or ammonia, and is a divalent structure in which two carbonyl ends are chemical bonds. From the viewpoint of obtaining a cured product with excellent heat resistance, the imide structure preferably forms a conjugated system together with the aromatic group. Since an imide structure contains a polar group, it generally tends to reduce moisture resistance. However, according to the present invention, even a resin composition containing a Bu polymer having an imide structure can obtain a cured product excellent in moisture resistance and heat resistance.
[0123] As the polyphenylene ether resin containing a PBu structure and a PPE structure, commercially available products can be used, for example, "BX-360", "BX-660", "BX-660M", and "BX-660T" manufactured by Nippon Kayaku Co., Ltd. can be used. As the polyimide resin containing a PBu structure and an imide structure, for example, Bu polymer a or a derivative thereof which can be synthesized in Synthesis Example 1 described later can be cited. As the cresol novolac resin containing a PBu structure and a PPO structure, for example, Bu polymer b or a derivative thereof which can be synthesized in Synthesis Example 2 described later can be cited.
[0124] The urethane bond that may be present between the butadiene skeleton (a1) and the aromatic group (a2) may be part of the linking group. The linking group is, for example, a divalent linking group. Examples of such a divalent linking group include a group derived from diisocyanate (for example, a group derived from toluene diisocyanate (i.e., -O(C=O)NH-ph(CH 3 )-NH(C=O)O-), a group derived from diphenylmethane diisocyanate (i.e., -O(C=O)NH-ph-CH 2 -ph-NH(C=O)O-), a group derived from isophorone diisocyanate (IPDI) (i.e., -O(C=O)NH-Ch(CH 3 ) 3 -CH 2-NH(C=O)O-)). The ester bond that may exist between the butadiene skeleton (a1) and the aromatic group (a2) may be a part of the connecting group. The connecting group is, for example, a divalent connecting group. As such a connecting group, a group derived from a dicarboxylic acid (for example, a group derived from terephthalic acid, a group derived from isophthalic acid (i.e., a group represented by -O(C=O)-ph-(C=O)O-)) is preferred. In the above formula, "ph" refers to a benzene ring, and "Ch" refers to a cyclohexane ring. In addition, in the above formula, the hydrogen bonded to the nitrogen atom may be substituted by any substituent.
[0125] In addition, component (A) preferably contains one or more monovalent groups containing a vinyl group (excluding "monovalent groups containing 3-butene-1,2-diyl"). Examples of the monovalent groups containing a vinyl group are (meth)acryloyl and (meth)acryloyloxy. Here, (meth)acryloyl includes acryloyl, methacryloyl and combinations thereof. In addition, (meth)acryloyloxy includes acryloyloxy, methacryloyloxy and combinations thereof.
[0126] Vinyl exists as a group that can form crosslinking points in addition to the double bonds contained in the butadiene skeleton, so the crosslinking points can be increased. The above-mentioned monovalent group containing vinyl is preferably present as an end group of the molecule constituting the (A) component, and more preferably exists as at least one end group of the two ends of the molecule of the Bu polymer.
[0127] The above-mentioned (A) component can be synthesized, for example, by block polymerization of a first resin (corresponding to the first monomer of the first block, such as "G3000" (number average molecular weight: 3000) manufactured by Nippon Soda Co., Ltd. or "SA90" manufactured by SABIC Corporation) which is a precursor containing a butadiene skeleton (a1) and a second resin (corresponding to the second monomer of the second block) which is a precursor containing an aromatic group (a2).
[0128] From the viewpoint of obtaining a cured product that more significantly exerts the desired effect of the present invention, the number average molecular weight (Mn) of component (A) is preferably 4,000 or more, more preferably 4,500 or more, particularly preferably 5,000 or more, preferably 100,000 or less, more preferably 90,000 or less, particularly preferably 80,000 or less.
[0129] From the viewpoint of obtaining a cured product that more significantly exerts the desired effect of the present invention, the weight average molecular weight (Mw) of component (A) is preferably 4000 or more, more preferably 10000 or more, particularly preferably 20000 or more, preferably 120000 or less, more preferably 110000 or less, particularly preferably 105000 or less. The weight average molecular weight of component (A) is a weight average molecular weight measured by gel permeation chromatography (GPC) in terms of polystyrene conversion.
[0130] From the viewpoint of obtaining a cured product that more significantly exhibits the desired effect of the present invention, the ratio of the weight average molecular weight to the number average molecular weight (Mw / Mn) of the component (A) is preferably between 1 and 30. The weight average molecular weight and number average molecular weight of the component (A) are weight average molecular weights in terms of polystyrene measured by gel permeation chromatography (GPC).
[0131] From the viewpoint of obtaining a flexible cured product, the content ratio (percentage) of the butadiene skeleton of the (A) component is preferably 30% by mass or more or 40% by mass or more, and from the viewpoint of obtaining a cured product with excellent flexibility, it is better to be set to 50% by mass or more, 60% by mass or more or 65% by mass or more. From the viewpoint of obtaining a cured product with excellent heat resistance and moisture resistance, the content ratio (percentage) of the butadiene skeleton of the (A) component can be set to, for example, 98% by mass or less, 95% by mass or less, less than 90% by mass or less than 85% by mass. Here, the content ratio (percentage) of the butadiene skeleton can be calculated by the ratio of the charge amount (parts by mass) of each material used to synthesize the (A) component. Alternatively, the molecular structure of the (A) component can be specified (specified) and calculated as the ratio of the formula weight of the butadiene skeleton part to the molecular weight. In the case of multiple (A) components, it is preferred that the average value of the content ratio (percentage) of the butadiene skeleton of each component according to the mass ratio of the component is within the aforementioned range.
[0132] When the non-volatile component in resin combination is set to 100 mass %, from the viewpoint of obtaining a flexible cured product, the content of (A) component can be set to be greater than 0 mass %, preferably set to more than 0.1 mass %, more than 1 mass %, more than 2 mass %, more than 3 mass %, more than 5 mass %, more than 9 mass % or more than 10 mass %.From the viewpoint of obtaining a cured product with excellent flexibility, when the non-volatile component in resin combination is set to 100 mass %, the content of (A) component is preferably more than 15 mass %, more than 16 mass %, more than 17 mass %, more than 18 mass %, more than 19 mass % or more than 20 mass %.From the viewpoint of obtaining a cured product with excellent heat resistance and moisture resistance, the content of (A) component is preferably determined according to the relative ratio of (B) component described later, when the non-volatile component in resin combination is set to 100 mass %, for example, can be set to less than 50 mass %, less than 50 mass %, less than 49 mass %, less than 45 mass %, less than 43 mass % or less than 40 mass %.
[0133] <(B) Inorganic fillers>
[0134] The resin composition contains an inorganic filler as component (B). By including the component (B) in the resin composition containing component (A), the flexibility of the cured product expected from component (A) can be greatly impaired, and a cured product with excellent heat resistance and moisture resistance can be obtained. Component (B) can be used alone or in combination of two or more.
[0135] As the material of the inorganic filler, an inorganic compound is used. As examples of the material of the inorganic filler, there can be mentioned: silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium phosphotungstate, etc. Among these, silicon dioxide is particularly preferred. As silicon dioxide, for example, amorphous silicon dioxide, fused silica, crystalline silicon dioxide, synthetic silicon dioxide, hollow silicon dioxide, etc. can be mentioned. In addition, as silicon dioxide, spherical silicon dioxide is preferred. (B) The inorganic filler can be used alone or in combination of two or more.
[0136] Commercially available products of component (B) include, for example, "UFP-30" manufactured by DENKA Corporation; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Corporation; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.
[0137] From the viewpoint of improving moisture resistance and dispersibility, component (B) is preferably treated with a surface treatment agent. As the surface treatment agent, for example, an amine coupling agent, a (meth) acrylic coupling agent, and a vinyl coupling agent can be cited, wherein, from the perspective of obtaining a cured product with excellent environmental test resistance (HAST resistance), it is better to use an amine coupling agent and a (meth) acrylic coupling agent. Here, an amine coupling agent refers to a coupling agent having an amino group. A (meth) acrylic coupling agent refers to a coupling agent having a methacryloyloxy group or an acryloxy group. A vinyl coupling agent refers to a coupling agent having a vinyl group, which is a coupling agent that does not belong to a (meth) acrylic coupling agent. The above-mentioned amine coupling agent, (meth) acrylic coupling agent, and vinyl coupling agent can each include a silane coupling agent, an alkoxysilane, an organic silazane compound, a titanate coupling agent, etc., and can belong to any of the silane coupling agents. As the silane coupling agent, for example, fluorine-containing silane coupling agents, epoxy silane coupling agents, and mercapto silane coupling agents can be cited. Among them, from the viewpoint of significantly obtaining the effect of the present invention, a silane coupling agent is preferred, and an amine coupling agent belonging to a silane coupling agent and a (meth) acrylic coupling agent belonging to a silane coupling agent are more preferred. In addition, the surface treatment agent can be used alone or in any combination of two or more.
[0138] Examples of commercially available surface treatment agents include KBM1003 (vinyl triethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., KBM503 (3-methacryloxypropyl triethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., KBM403 (3-glycidoxypropyl trimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., KBM803 (3-mercaptopropyl trimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., KBE903 (3-aminopropyl trimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd. "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane) made by Shin-Etsu Chemical Co., Ltd., etc. Among them, it is preferred to use one or more selected from "KBM503" belonging to the (meth)acryloyloxy coupling agent and "KBM573" and "KBE903" belonging to the amine coupling agent, and it is more preferred to use at least one of "KBM503" and "KBM573".
[0139] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment performed with a surface treatment agent is preferably within a specified range. Specifically, 100 parts by mass of the inorganic filler is preferably surface treated with 0.2 to 5 parts by mass of a surface treatment agent, preferably with 0.2 to 3 parts by mass of a surface treatment agent, and preferably with 0.3 to 2 parts by mass of a surface treatment agent.
[0140] The degree of surface treatment by the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is preferably 0.02 mg / m 2 More than 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of suppressing the increase of the melt viscosity of the resin varnish and the melt viscosity in the sheet form, 1 mg / m 2 Below, preferably 0.8mg / m 2 Below, more preferably 0.5 mg / m 2 the following.
[0141] The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added as a solvent to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid component, a carbon analyzer can be used to measure the amount of carbon per unit surface area of the inorganic filler. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. can be used.
[0142] The specific surface area of component (B) is preferably 1 m 2 / g or more, preferably 2m 2 / g or more, particularly preferably 3m 2 There is no particular upper limit, but it is preferably 60 m 2 / g or less, 50m 2 / g or below or 40m 2 The specific surface area can be obtained by adsorbing nitrogen gas on the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method and calculating the specific surface area by the BET multipoint method.
[0143] From the viewpoint of significantly obtaining the desired effect of the present invention, the average particle size of the component (B) is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, and preferably 5 μm or less, more preferably 2 μm or less, further preferably 1 μm or less.
[0144] The average particle size of (B) component can be measured by laser diffraction-scattering method based on Mie scattering theory. Specifically, the particle size distribution of inorganic filler can be made into a volume basis by laser diffraction scattering particle size distribution measuring device, and the median particle size can be measured as the average particle size. The sample can be measured using a sample obtained by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. For the sample, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source is set to blue and red, and the particle size distribution of the volume basis of (B) component is measured in a flow cell (flowcell) manner, and the average particle size is calculated as the median particle size according to the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba, Ltd. can be cited.
[0145] From the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance, when the non-volatile component in the resin composition is set to 100% by mass, the content of component (B) is greater than 0% by mass, for example, it can be set to more than 0.1% by mass, more than 1% by mass, more than 2% by mass, more than 3% by mass, more than 4% by mass, more than 5% by mass, more than 6% by mass, more than 7% by mass, more than 8% by mass, more than 9% by mass or more than 10% by mass. From the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance, when the non-volatile component in the resin composition is set to 100% by mass, the content of component (B) can be set to less than 60% by mass, less than 55% by mass, less than 50% by mass, less than 50% by mass, less than 45% by mass, less than 41% by mass or less than 40% by mass. From the viewpoint of obtaining a cured product having excellent flexibility, when the non-volatile component in the resin composition is set to 100 mass %, the content of component (B) can be set to 50 mass % or less, less than 50 mass %, 45 mass % or less, 43 mass % or less, 41 mass % or less, or 40 mass % or less.
[0146] The amount (mass parts) of (B) component in resin combination relative to the mass ratio (mass %) of the amount (mass parts) of (A) component (hereinafter also referred to as "B / A ratio") is preferably determined from the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance within the range of the flexibility of the cured product obtained by (A) component, and can be set to, for example, more than 50 mass %, more than 75 mass % or more than 100 mass %. Here, B / A ratio refers to the ratio (percentage) of the content of (B) component when the content of (A) component is set to 100 mass %. From the viewpoint of obtaining a cured product having excellent flexibility, heat resistance and moisture resistance, B / A ratio can be set to less than 250 mass %, less than 200 mass % or less than 175 mass %.
[0147] The mass ratio (mass %) of "the amount (mass parts) of component (B)" to "the total amount (mass parts) of component (A) and the amount (mass parts) of component (C) described later" (hereinafter also referred to as "B / (A+C) ratio") is preferably determined from the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance within a range that does not significantly impair the flexibility of the cured product obtained from component (A), and can be set, for example, to 15 mass % or more, 20 mass % or more, or 25 mass % or more. Here, the B / (A+C) ratio refers to the ratio (percentage) of the content of component (B) when the total content of component (A) and the content of component (C) is set to 100 mass %. From the viewpoint of obtaining a cured product having excellent flexibility, heat resistance and moisture resistance, the B / (A+C) ratio can be set to 70 mass % or less, 65 mass % or less, or 60 mass % or less.
[0148] <(C) Benzoxazine compounds containing substituted or unsubstituted allyl groups>
[0149] The resin composition contains a "benzoxazine compound containing a substituted or unsubstituted allyl group" (hereinafter also referred to as an "allyl-containing benzoxazine compound") as the (C) component. The benzoxazine compound refers to a compound having the following benzoxazine structure. By including the (C) component in the resin composition containing the (A) components and the (B) components, the flexibility of the cured product expected by the (A) component is not significantly impaired, and a cured product with better heat resistance and moisture resistance can be obtained. The reason is believed to be that the (C) component functions as a curing agent that thermally cures the resin composition through the reactivity of the allyl group and the reactivity of the benzoxazine structure, thereby forming a cross-linked structure (matrix) in the cured product. As a result, even if the (A) component and the (B) component contain a site with poor heat resistance (e.g., a butadiene skeleton (a1)) and a hydrophilic or hygroscopic site (a polar group, an imide structure, a hydrophilic group on the surface of silica), by allowing the (A) component and the (B) component to enter the cross-linked structure, a hydrophobic and heat-resistant cured product is formed as a whole, and the heat resistance of the cured product is synergistically improved by the heat-resistant sites (e.g., aromatic groups (b1) and inorganic filler particles themselves) contained in the (A) component and the (B) component. Here, when the (A) component has a vinyl group at the molecular end, it can react with the (C) component to form a cross-linked structure. In addition, according to the present invention, by using the components (B) and (C) in combination, it is possible to improve both the heat resistance and moisture resistance of the cured product of a resin composition containing a component (e.g., component (A)) having a portion with poor heat resistance in the molecule (e.g., a butadiene skeleton).
[0150] (C) component contains at least one benzoxazine structure in the molecule. The benzoxazine structure may be substituted by any substituent as long as the ring-opening reaction of the benzoxazine structure is not excessively hindered. In addition, a portion of the double bonds contained in the benzoxazine structure may be hydrogenated. For the benzoxazine structure, for example, there are 1,2-benzoxazine structures and 1,3-benzoxazine structures, among which, from the viewpoint of obtaining the desired effect of the present invention, the 3,4-dihydro-2H-1,3-benzoxazine structure shown in the following formula (c1) is preferred.
[0151] [Chemical formula 17]
[0152]
[0153] (In the above formula (c1), * represents a chemical bond or a hydrogen atom).
[0154] The number of benzoxazine structures per molecule of component (C) is 1 or more, preferably 2 or more from the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance, and the upper limit is not limited and can be 10 or less, 6 or less, 4 or less, or 3 or less.
[0155] In addition, component (C) contains at least one substituted or unsubstituted allyl group in the molecule. Unsubstituted allyl group is 2-propylene group. For allyl group, as long as its reactivity is not too hindered, it can have any substituent. An example of a substituted allyl group is 2-methylallyl group. From the viewpoint of obtaining a cured product with excellent heat resistance and moisture resistance, the number of allyl groups per molecule in component (C) is preferably the same as or more than the number of benzoxazine structures per molecule in component (C), preferably more than 2, more preferably more than 4, and the upper limit is not limited, and can be set to less than 20, less than 12, less than 8, or less than 6.
[0156] In the component (C), from the viewpoint of remarkably obtaining the desired effect of the present invention, the allyl group is preferably bonded to any of a nitrogen atom constituting the benzoxazine structure and a carbon atom constituting the benzoxazine structure, more preferably bonded to a carbon atom constituting the benzoxazine structure.
[0157] The first example of the component (C) is a first allyl group-containing benzoxazine compound represented by the following formula (C1-1);
[0158] [Chemical formula 18]
[0159]
[0160] (In the above formula (C1-1), R 20 and R 21 Each independently represents a substituted or unsubstituted allyl group, R 22 represents a q-valent group. q represents an integer of 1 to 10, p1s each independently represent an integer of 0 to 4, and p2s each independently represent an integer of 0 to 2).
[0161] R 22 The q-valent group represented by is preferably a q-valent group selected from a substituted or unsubstituted allyl group, a q-valent aromatic hydrocarbon group, a q-valent aliphatic hydrocarbon group, an oxygen atom, and a combination thereof. At least one of the hydrogen atoms possessed by the q-valent aromatic hydrocarbon group and the q-valent aliphatic hydrocarbon group may be substituted by a halogen atom. 22 In the case of a substituted or unsubstituted allyl group, q=1, and in this case, both p1 and p2 may be 0. 22 In the case of a substituted or unsubstituted allyl group, the allyl group may be a substituent of any of a q-valent aromatic hydrocarbon group and a q-valent aliphatic hydrocarbon group. For example, when q is 2, R 22An arylene group, an alkylene group, an oxygen atom or a group composed of a combination of two or more divalent groups thereof is preferred, an arylene group or a group composed of a combination of two or more divalent groups is more preferred, and a group composed of a combination of two or more divalent groups is further preferred.
[0162] As R 22 The arylene group in is preferably an arylene group having 6 to 20 carbon atoms, more preferably an arylene group having 6 to 15 carbon atoms, and still more preferably an arylene group having 6 to 12 carbon atoms. Specific examples of the arylene group include phenylene, naphthylene, anthrylene, biphenylene and the like, and phenylene is preferred.
[0163] As R 22 The alkylene group in is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and still more preferably an alkylene group having 1 to 3 carbon atoms. Specific examples of the alkylene group include methylene, ethylene, propylene, and the like, and methylene is preferred.
[0164] As R 22 The group composed of two or more divalent groups in the group may include, for example, a group composed of one or more arylene groups bonded to one or more oxygen atoms; a group composed of one or more arylene groups bonded to one or more alkylene groups such as a group having an arylene-alkylene-arylene structure; a group composed of one or more alkylene groups bonded to one or more oxygen atoms; a group composed of one or more arylene groups, one or more alkylene groups, and one or more oxygen atoms, etc., preferably a group composed of one or more arylene groups bonded to one or more oxygen atoms, or a group composed of one or more arylene groups bonded to one or more alkylene groups.
[0165] q represents an integer of 1 to 10, preferably an integer of 1 to 4, more preferably an integer of 1 to 3, further preferably 1 or 2.
[0166] p1 each independently represents an integer of 0 to 4, preferably an integer of 0 to 2, more preferably 0 or 1, further preferably 1. p2 each independently represents an integer of 0 to 2, 0 or 1, preferably 0.
[0167] From the viewpoint of obtaining the desired effects of the present invention, the benzoxazine compound represented by the general formula (C1-1) is preferably an allyl group-containing benzoxazine compound represented by the following general formula (C1-1a).
[0168] [Chemical formula 19]
[0169]
[0170] (In the above formula (C1-1a), R 20 , R21 and R 23 Each independently represents a substituted or unsubstituted allyl group, p1' each independently represents an integer of 0 to 4, p2' each independently represents an integer of 0 to 2, and p3' each independently represents an integer of 0 to 4. At least one of the plurality of p1', p2' and p3' represents an integer greater than 1).
[0171] The allyl group-containing benzoxazine compound represented by the general formula (C1-1a) is preferably a benzoxazine compound represented by the formula (C1-1b).
[0172] [Chemical formula 20]
[0173]
[0174] (In the above formula (C1-1b), R 20 , R 21 , p1' and p2' are respectively the same as R in the above formula (C1-1a) 20 , R 21 , p1' and p2' have the same meaning).
[0175] As the first benzoxazine compound containing an allyl group, a commercial product can be used. As a commercial product, for example, "ALP-d" (a Pd-type benzoxazine compound containing an allyl group having the structure of the above formula (C1-1a)) manufactured by Shikoku Chemical Industry Co., Ltd. can be cited. In addition, the first benzoxazine compound containing an allyl group can use a benzoxazine compound disclosed in Japanese Patent Publication No. 2016-074871 or a derivative thereof. It should be noted that the first benzoxazine compound containing an allyl group can be manufactured according to the method described in Japanese Patent Publication No. 2016-074871.
[0176] The second example of the component (C) is a second allyl group-containing benzoxazine compound represented by the following formula (C2-1);
[0177] [Chemical formula 21]
[0178]
[0179] (In the above formula (C2-1), R 20a , R 21a and R 22a Each independently represents a substituted or unsubstituted allyl group, R 22 ' represents a q'-valent group bonded to a carbon atom of the benzoxazine ring. q' represents an integer of 1 to 10, p1a each independently represents an integer of 0 to 4, p2a each independently represents an integer of 0 to 2, and R 22 'For each combined benzoxazine structure, the maximum value of the sum of p1a and p2a is 5).
[0180] R 20a , R 21a and R 22a At least one of them is preferably a substituted or unsubstituted allyl group, R 20a , R 21a and R 22a When all are not substituted or unsubstituted allyl groups, R 22' It has at least one substituted or unsubstituted allyl group.
[0181] R 22' The q'-valent group represented by is preferably a q'-valent group selected from a q'-valent aromatic hydrocarbon group, a q'-valent aliphatic hydrocarbon group, an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, and a combination thereof. At least one of the hydrogen atoms in the q'-valent aromatic hydrocarbon group and the q'-valent aliphatic hydrocarbon group may be substituted with a halogen atom or a substituted or unsubstituted allyl group. For example, when q' is 2, R 22' It is preferably a group selected from an arylene group, an alkylene group, an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group and a combination of two or more divalent groups thereof.
[0182] As R 22' The arylene group in is preferably an arylene group having 6 to 20 carbon atoms, more preferably an arylene group having 6 to 15 carbon atoms, and still more preferably an arylene group having 6 to 12 carbon atoms. Specific examples of the arylene group include phenylene, naphthylene, anthrylene, biphenylene and the like, and phenylene is preferred.
[0183] As R 22' The alkylene group in is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and still more preferably an alkylene group having 1 to 3 carbon atoms. Specific examples of the alkylene group include methylene, ethylene, propylene, and the like, and methylene is preferred.
[0184] As R 22' The group composed of two or more divalent groups in the group may include, for example, a group composed of one or more arylene groups bonded to one or more oxygen atoms; a group composed of one or more arylene groups bonded to one or more alkylene groups, such as a group having an arylene-alkylene-arylene structure; a group composed of one or more alkylene groups bonded to one or more oxygen atoms; a group composed of one or more arylene groups, one or more alkylene groups, and one or more oxygen atoms, etc., preferably a group composed of one or more arylene groups bonded to one or more oxygen atoms, or a group composed of one or more arylene groups bonded to one or more alkylene groups.
[0185] q' represents an integer of 1 to 10, preferably an integer of 1 to 4, more preferably an integer of 1 to 3, and further preferably 1 or 2. When q' is an integer of 2 or more, 22' The q' benzoxazine structures and their substituents that are bonded may be the same as or different from each other.
[0186] p1a each independently represents an integer of 0 to 4, preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 1. p2a each independently represents an integer of 0 to 2, 0 or 1, and preferably 0. 22' For each combined benzoxazine structure, the maximum value of the sum of p1a and p2a is 5.
[0187] As the second allyl group-containing benzoxazine compound, a benzoxazine compound disclosed in JP-A-2016-074871 or a derivative thereof can be used. It should be noted that the second allyl group-containing benzoxazine compound can be produced according to the method described in JP-A-2016-074871.
[0188] The third example of the component (C) is a third allyl-containing benzoxazine compound that is not one of the first allyl-containing benzoxazine compound and the second allyl-containing benzoxazine compound. The third allyl-containing benzoxazine compound includes an allyl-containing benzoxazine compound that contains a 1,2-benzoxazine structure or a 1,4-benzoxazine structure and can undergo a ring-opening reaction.
[0189] The molecular weight of the component (C) is preferably at least 200, more preferably at least 300, further preferably at least 400, and is preferably at most 1,000, more preferably at most 800, further preferably at most 500, from the viewpoint of improving adhesion.
[0190] From the viewpoint of significantly obtaining the desired effect of the present invention, the equivalent weight of the benzoxazine structure of the component (C) (hereinafter also referred to as "ring-opening reaction participating group equivalent weight") is preferably 100 g / eq. to 1000 g / eq., more preferably 150 g / eq. to 500 g / eq., and further preferably 200 g / eq. to 300 g / eq. The ring-opening reaction participating group equivalent weight is the mass of the allyl group-containing benzoxazine compound containing 1 equivalent of the ring-opening reaction participating group (benzoxazine structure).
[0191] From the viewpoint of significantly obtaining the desired effect of the present invention, the allyl equivalent of the component (C) is preferably 100 to 1000 g / eq., more preferably 150 to 500 g / eq., further preferably 200 to 300 g / eq. The allyl equivalent is the mass of the allyl-containing benzoxazine compound including 1 equivalent of allyl groups.
[0192] For the content of (C) component, it is preferred that (C) component can constitute the amount of the cross-linked structure that can exert the desired effect of the present invention between (C) component or with other components, and when the non-volatile component in the resin combination is set to 100% by mass, the content of (C) component can be set to, for example, more than 0.01% by mass, more than 0.02% by mass, more than 0.03% by mass, more than 1% by mass, more than 2% by mass or more than 3% by mass. The upper limit is not particularly limited, for example, less than 30% by mass, less than 25% by mass, less than 20% by mass, less than 15% by mass or less than 10% by mass. From the viewpoint of obtaining a cured product with excellent flexibility, when the non-volatile component in the resin combination is set to 100% by mass, the content of (C) component is preferably less than 20% by mass, more preferably less than 15% by mass, and further more preferably less than 10% by mass. In addition, the content of (C) component is preferably set according to the ring-opening reaction participating group equivalent and allyl equivalent of (C) component.
[0193] In addition, from the viewpoint of exerting the desired effect of the present invention, the content of (C) component is preferably less than the total content of (A) component and (B) component. From the viewpoint of exerting the desired effect of the present invention, the mass ratio (mass %) of "the amount (mass parts) of (C) component" in the resin composition relative to "the total amount (mass parts) of (A) component and (B) component" (hereinafter also referred to as "C / (A+B) ratio"), for example, can be set to more than 1 mass %, more than 2 mass %, more than 3 mass %, more than 4 mass % or more than 5 mass %. Here, C / (A+B) ratio refers to the ratio (percentage) of the content of (C) component when the total content of (A) component and (B) component is set to 100 mass %. From the viewpoint of obtaining a cured product having excellent flexibility, heat resistance and moisture resistance, C / (A+B) ratio is usually less than 100 mass %, preferably less than 30 mass %, more preferably less than 25 mass %, and further preferably less than 20 mass %.
[0194] <(D) Thermosetting resin>
[0195] The resin composition of the present invention may further contain (D) a thermosetting resin. The (D) thermosetting resin does not contain substances belonging to the (A) component and the (C) component. As the (D) thermosetting resin, one or more resins selected from any resin having thermosetting properties (hereinafter also referred to as "(D-1) component") and a resin that functions as a curing agent (hereinafter also referred to as "(D-2) component") can be used.
[0196] (D-1) component is not particularly limited, and examples thereof include epoxy resin, polyester resin, polyurethane resin, polyester polyurethane resin, butyral resin, acrylic resin, cyanate resin, silicone resin, oxetane resin, melamine resin, maleimide resin, etc., wherein epoxy resin is preferred. In addition, in a certain embodiment, (D-1) component is one or more resins selected from epoxy resin, polyester resin, polyurethane resin, polyester polyurethane resin, butyral resin, acrylic resin, cyanate resin, silicone resin, oxetane resin, and melamine resin. That is, in this embodiment, maleimide resin is removed from (D-1) component, thereby obtaining a varnish having excellent compatibility.
[0197] Examples of the epoxy resin include biphenyl epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidylester epoxy resins, cresol novolac epoxy resins, biphenyl epoxy resins, linear aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane epoxy resins, cyclohexanedimethanol epoxy resins, naphthylene ether epoxy resins, trimethylol epoxy resins, tetraphenylethane epoxy resins, and the like. The epoxy resins may be used alone or in combination of two or more.
[0198] Resin combination is preferably included in an epoxy resin having more than 2 epoxy groups as epoxy resin in one molecule. From the viewpoint of significantly obtaining the desired effect of the present invention, relative to 100 mass % of the non-volatile component of epoxy resin, the ratio of the epoxy resin having more than 2 epoxy groups in one molecule is preferably more than 50 mass %, more preferably more than 60 mass %, and particularly preferably more than 70 mass %.
[0199] The epoxy resin includes an epoxy resin that is liquid at a temperature of 20° C. (hereinafter sometimes referred to as “liquid epoxy resin”) and an epoxy resin that is solid at a temperature of 20° C. (hereinafter sometimes referred to as “solid epoxy resin”). The resin composition of the present invention may contain only a liquid epoxy resin or only a solid epoxy resin as the epoxy resin, and preferably contains a combination of a liquid epoxy resin and a solid epoxy resin.
[0200] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0201] As liquid epoxy resins, preferred are bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, and glycidyl amine type epoxy resins.
[0202] Specific examples of liquid epoxy resins include: "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "EPIKOTE 828EL" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemicals; "EX-721" (glycidyl ester-type epoxy resin) manufactured by Nagase ChemteX; and "Celloxide 2021P" (alicyclic epoxy resin with an ester skeleton); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd., etc. They can be used alone or in combination of two or more.
[0203] The solid epoxy resin is preferably a solid epoxy resin having three or more epoxy groups in one molecule, and more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule.
[0204] As solid epoxy resins, preferred are biphenyl type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, and tetraphenylethane type epoxy resins.
[0205] Specific examples of solid epoxy resins include: "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", and "HP-7200H" (dicyclopentadiene epoxy resin) manufactured by DIC Corporation; "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthyl ether type epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000 L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthol type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "YX4000H", "YX4000", "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX4000HK" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation "YX7700" manufactured by Mitsubishi Chemical Corporation (a novolac epoxy resin containing a xylene structure); "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" manufactured by Mitsubishi Chemical Corporation (a bisphenol AF epoxy resin); "YL7800" manufactured by Mitsubishi Chemical Corporation (a fluorene epoxy resin); "jER1010" manufactured by Mitsubishi Chemical Corporation (a solid bisphenol A epoxy resin); "jER1031S" manufactured by Mitsubishi Chemical Corporation (a tetraphenylethane epoxy resin), etc. These may be used alone or in combination of two or more.
[0206] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio of them (liquid epoxy resin: solid epoxy resin) is preferably 1:1 to 1:50, more preferably 1:3 to 1:30, and particularly preferably 1:5 to 1:20. By making the mass ratio of the liquid epoxy resin to the solid epoxy resin within the above range, the desired effect of the present invention can be significantly obtained.
[0207] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further preferably 110 g / eq. to 1000 g / eq. By being within this range, the crosslinking density of the cured product of the resin composition becomes sufficient, and an insulating layer with a small surface roughness can be provided. The epoxy equivalent is the mass of a resin containing 1 equivalent of an epoxy group. The epoxy equivalent can be measured according to JIS K7236.
[0208] From the viewpoint of remarkably obtaining the desired effect of the present invention, the weight average molecular weight (Mw) of the epoxy resin is preferably from 100 to 5000, more preferably from 250 to 3000, further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).
[0209] The content of component (D-1) is not particularly limited. From the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance, when the non-volatile component in the resin combination is set to 100% by mass, it is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. The upper limit of the content of component (D-1) is not particularly limited. From the viewpoint of obtaining a cured product having excellent flexibility, heat resistance and moisture resistance, when the non-volatile component in the resin combination is set to 100% by mass, it is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 35% by mass or less.
[0210] The resin that functions as the (D-2) curing agent (which does not include the (D-1) component) is preferably a substance that has the function of curing at least one of the (C) component and the (D-1) component. The (D-2) component is not particularly limited. When the (D-1) component is an epoxy resin, for example, phenol-based curing agents, naphthol-based curing agents, acid anhydride-based curing agents, active ester-based curing agents, benzoxazine-based curing agents, cyanate-based curing agents, and carbodiimide-based curing agents can be cited. It is preferably each resin that functions as any one of the phenol-based curing agents, naphthol-based curing agents, and active ester-based curing agents (hereinafter also referred to as "curing agent"). The (D-2) component preferably contains a resin that functions as an active ester-based curing agent. The (D-2) component can be used alone or in combination of two or more.
[0211] As phenolic curing agent and naphthol curing agent, from the viewpoint of heat resistance and water resistance, preferably, there is a phenolic curing agent with a novolac structure or a naphthol curing agent with a novolac structure. In addition, from the viewpoint of adhesion with the adherend, preferably, a nitrogen-containing phenolic curing agent or a nitrogen-containing naphthol curing agent, more preferably, a phenolic curing agent containing a triazine skeleton or a naphthol curing agent containing a triazine skeleton. Among them, from the viewpoint of highly satisfying heat resistance, water resistance and adhesion, preferably, a phenolic novolac resin containing a triazine skeleton. Specific examples of phenol-based curing agents and naphthol-based curing agents include: "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel & Sumitomo Chemicals; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.
[0212] Examples of the acid anhydride curing agent include curing agents having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dicarboxylic anhydride, and the like. Benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride ester), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, etc. Examples of commercially available acid anhydride curing agents include "HNA-100" and "MH-700" manufactured by Shin Nippon Rika Co., Ltd.
[0213] As active ester curing agent, there is no particular restriction, and it is usually preferred to use phenolic esters, thiophenolic esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc., compounds having ester groups with high reactive activity of more than 2 in one molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. In particular, from the viewpoint of improving heat resistance, it is preferably an active ester curing agent obtained by carboxylic acid compounds and hydroxy compounds, and more preferably an active ester curing agent obtained by carboxylic acid compounds and phenolic compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, phenol novolac resins, etc. Here, the so-called "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol on one molecule of dicyclopentadiene.
[0214] Specifically, preferred are active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing acetylated products of phenol novolac resins, and active ester compounds containing benzoylated products of phenol novolac resins. Among them, more preferred are active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure. The so-called "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit formed of phenylene-dicyclopentalene-phenylene.
[0215] Commercially available active ester curing agents include: "EXB9451", "EXB9460", "EXB9460S", "HPC-8000", "HPC-8000H", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM" (manufactured by DIC Corporation), which are active ester compounds containing a dicyclopentadiene-type diphenol structure; "EXB9416-70BK", "EXB-8150-65T" and "EXB-8150-65T" which are active ester compounds containing a naphthalene structure. (manufactured by DIC Corporation); "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing an acetylated product of a phenol novolac resin; "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing a benzoylated product of a phenol novolac resin; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent that is an acetylated product of a phenol novolac resin; "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester curing agents that are benzoylated products of a phenol novolac resin; and the like.
[0216] Specific examples of the benzoxazine-based curing agent include “JBZ-OP100D” and “ODA-BOZ” manufactured by JFE Chemical Industry Co., Ltd.; “HFB2006M” manufactured by Showa High Molecular Co., Ltd.; and “Pd” and “Fa” manufactured by Shikoku Chemical Industry Co., Ltd.
[0217] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are phenol novolac-type multifunctional cyanate resins), "BA230", "BA230S75" (prepolymers obtained by triazine-forming a part or all of bisphenol A dicyanate to form a trimer), etc.
[0218] Specific examples of the carbodiimide-based curing agent include "V-03" and "V-07" manufactured by Nisshinbo Chemical Co., Ltd.
[0219] When the resin composition contains component (D-2), the amount ratio of component (D-1) to component (D-2) is preferably in the range of 1:0.2 to 1:2, more preferably 1:0.3 to 1:1.5, and further preferably 1:0.4 to 1:1.2, based on the ratio of [the total number of reactive groups of component (D-1)]:[the total number of reactive groups of component (D-2)]. Here, the reactive group of component (D-1) refers to an epoxy group or the like, which varies depending on the type of component (D-1). The reactive group of component (D-2) refers to an active hydroxyl group, an active ester group, or the like, which varies depending on the type of component (D-2).
[0220] When the resin composition contains (D-2) component, its content is not particularly limited, and when the non-volatile component in the resin composition is set to 100 mass %, it can be set to, for example, 0.1 mass %, 1 mass % or more, or 3 mass % or more. The upper limit of the content of (D-2) component is not particularly limited, and when the non-volatile component in the resin composition is set to 100 mass %, it can be set to 30 mass %, 25 mass % or less, or 20 mass % or less.
[0221] The content of (D) component is not particularly limited. From the viewpoint of obtaining a cured product having excellent heat resistance and moisture resistance, when the non-volatile component in the resin composition is set to 100% by mass, the content of (D) component is preferably 5.1% by mass or more, more preferably 11% by mass or more, and further preferably 18% by mass or more. The upper limit of the content of (D) component is not particularly limited. From the viewpoint of obtaining a cured product having excellent flexibility, heat resistance and moisture resistance, when the non-volatile component in the resin composition is set to 100% by mass, it is preferably 80% by mass or less, more preferably 65% by mass or less, and further preferably 55% by mass or less.
[0222] <(E) Curing accelerator>
[0223] The resin composition of the present invention may contain (E) a curing accelerator as an optional component. The (E) curing accelerator has a function of accelerating the curing rate of the resin component (for example, the (C) component and the (D) component).
[0224] (E) curing accelerator is not particularly limited. When component (D-1) is an epoxy resin, for example, phosphorus curing accelerator, amine curing accelerator, imidazole curing accelerator, guanidine curing accelerator, metal curing accelerator, peroxide curing accelerator, etc. can be cited. Among them, phosphorus curing accelerator, amine curing accelerator, imidazole curing accelerator, metal curing accelerator, peroxide curing accelerator are preferred, and amine curing accelerator and peroxide curing accelerator are more preferred. One curing accelerator can be used alone, or two or more can be used in combination.
[0225] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate.
[0226] Examples of the amine curing accelerator (hereinafter also referred to as "component (E-1)") include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, and the like, preferably 4-dimethylaminopyridine.
[0227] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1' )]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline and other imidazole compounds, and adducts of imidazole compounds with epoxy resins.
[0228] As the imidazole-based curing accelerator, a commercially available item may be used, and examples thereof include "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0229] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0230] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. As specific examples of organic metal complexes, organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II) can be cited. As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0231] Examples of the peroxide-based curing accelerator (hereinafter also referred to as "component (E-2)") include peroxides such as tert-butyl cumene peroxide, tert-butyl peroxyacetate, α,α'-di(tert-butylperoxy)diisopropylbenzene, tert-butyl peroxylaurate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxybenzoate, and di-tert-hexyl peroxide.
[0232] Examples of commercially available peroxide-based curing accelerators include “PERBUTYL (registered trademark) C,” “PERBUTYL (registered trademark) A,” “PERBUTYL (registered trademark) P,” “PERBUTYL (registered trademark) L,” “PERBUTYL (registered trademark) O,” “PERBUTYL (registered trademark) ND,” “PERBUTYL (registered trademark) Z,” “PERBUTYL (registered trademark) I,” “PERCUMYL P,” “PERCUMYL D,” “PERHEXYL (registered trademark) D,” “PERHEXYL (registered trademark) A,” “PERHEXYL (registered trademark) I,” “PERHEXYL (registered trademark) Z,” “PERHEXYL (registered trademark) ND,” “PERHEXYL (registered trademark) O,” “PERHEXYL (registered trademark) PV,” and “PERHEXYL (registered trademark) O,” all manufactured by NOF Corporation.
[0233] When the resin composition contains (E) a curing accelerator, its content is not particularly limited, and when the non-volatile component in the resin composition is set to 100% by mass, it is preferably more than 0.001% by mass, more preferably more than 0.01% by mass, and further more preferably more than 0.02% by mass. The upper limit of the content of the (E) curing accelerator is not particularly limited, and when the non-volatile component in the resin composition is set to 100% by mass, it is preferably less than 2% by mass, more preferably less than 1% by mass, and further more preferably less than 0.5% by mass.
[0234] <(F) Other additives>
[0235] The resin composition of the present invention may further contain any additive as a non-volatile component. Examples of such additives include: thermoplastic resins such as phenoxy resins, polyvinyl acetal resins, polyolefin resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyetheretherketone resins, polyester resins, etc.; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as siloxane; thickeners such as bentonite and montmorillonite; silicone-based defoamers, acrylic defoamers, and fluorine-based defoamers. Defoaming agents such as defoaming agents, vinyl resin defoaming agents, etc.; UV absorbers such as benzotriazole UV absorbers; adhesion enhancers such as urea silane; adhesion imparting agents such as silane coupling agents, triazole adhesion imparting agents, tetrazole adhesion imparting agents, and triazine adhesion imparting agents; antioxidants such as hindered phenol antioxidants and hindered amine antioxidants; fluorescent whitening agents such as stilbene derivatives; flame retardants such as phosphorus flame retardants (such as phosphate compounds, phosphazene compounds, phosphonic acid compounds, and red phosphorus), nitrogen flame retardants (such as melamine sulfate), halogen flame retardants, and inorganic flame retardants (such as antimony trioxide); etc. The additives can be used alone or in combination of two or more in any ratio. For those skilled in the art, the content of (F) other additives can be appropriately set.
[0236] <(G) Organic solvent>
[0237] In addition to the above-mentioned non-volatile components, the resin composition of the present invention sometimes further contains an arbitrary organic solvent as a volatile component. As the (G) organic solvent, any known solvent can be appropriately used as long as it is a solvent that can dissolve at least a part of the non-volatile components, and its type is not particularly limited. As the (G) organic solvent, for example: ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, etc.; alcohol solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, carbitol acetate (ethyl diglycol Ether ester solvents such as acetate, diethylene glycol monoethyl ether acetate), γ-butyrolactone, methoxypropionic acid methyl ester, etc.; ester alcohol solvents such as methyl lactate, ethyl lactate, 2-hydroxyisobutyric acid methyl ester, etc.; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, diethylene glycol monobutyl ether (butyl carbitol), etc.; amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc.; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, methylcyclohexane, etc.; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, trimethylbenzene, etc.; etc. The organic solvent may be used alone or in combination of two or more in any ratio.
[0238] For the content of (G) organic solvent, from the viewpoint of effectively carrying out the drying of resin combination, can be with non-volatile component relative to the mass ratio of resin combination gross mass, i.e. solid component ratio, become preferably more than 30 mass %, more preferably more than 35 mass %, further more preferably more than 40 mass %, especially preferably more than 45 mass % mode and set.The upper limit of solid component ratio is not particularly limited, from the viewpoint of the handleability of resin combination, preferably below 100 mass %, more preferably below 95 mass %, further more preferably below 92 mass %, especially preferably below 90 mass %.
[0239] <Method for producing resin composition>
[0240] The resin combination of the present invention can be manufactured in the following manner, for example: in any order and / or partially or entirely simultaneously, (A) component, (B) component and (C) component, (D) component used as needed, (E) component used as needed, (G) component used as needed, (H) component used as needed are added to any reaction vessel and mixed. In addition, in the process of adding each component and mixing, the temperature can be appropriately set, and heating and / or cooling can be performed temporarily or throughout. In addition, in the process of adding each component and mixing, stirring or vibration can be performed. In addition, when adding and mixing or afterwards, stirring devices such as mixers can be used to stir the resin combination so that it is evenly dispersed.
[0241] <Physical properties and uses of resin composition>
[0242] The resin composition of the present invention is a resin composition comprising a polymer containing a butadiene skeleton, (B) an inorganic filler and (C) a benzoxazine compound containing a substituted or unsubstituted allyl group, wherein when the non-volatile component in the resin composition is set to 100% by mass, the content of the inorganic filler (B) is 60% by mass or less and greater than 0% by mass. By using these components in combination, as illustrated in the embodiment, a cured product having excellent heat resistance and moisture resistance can be obtained. In addition, the cured product includes a polymer containing a butadiene skeleton (A), so it is flexible. As a reason for achieving this effect, it is believed that the resin composition can form a moderate cross-linked structure by including (C) components, and the result of taking in (A) components and (B) components in the cross-linked structure.
[0243] The cured product obtained by heat curing the resin composition according to the present embodiment at 180° C. for 30 minutes showed little peeling after the heat resistance test. The heat resistance test can be carried out by the method described in the examples described below. Therefore, the cured product of the resin composition of the present invention has excellent heat resistance.
[0244] The cured product obtained by heat curing the resin composition involved in the present embodiment at 200° C. for 90 minutes shows a small water absorption value. The water absorption value can be measured by the method described in the embodiments described later. Specifically, the water absorption value of the cured product of the resin composition of the present invention is preferably less than 0.20%, and more preferably less than 0.19%. Therefore, the cured product of the resin composition of the present invention has excellent moisture resistance.
[0245] In addition, the resin composition of the present invention can bring an insulating layer formed by a cured product having excellent heat resistance and moisture resistance. Therefore, the resin composition of the present invention can be suitably used as: a resin composition for forming an insulating layer, a resin composition for a printed wiring board containing an insulating layer. The cured product of the resin composition of the present invention has flexibility. Therefore, the resin composition of the present invention can be suitably used as: a resin composition for a flexible substrate containing an insulating layer. In addition, the resin composition of the present invention can also be suitably used as a resin composition other than an insulating application.
[0246] [Resin sheet]
[0247] The resin sheet of the present invention includes a support and a resin composition layer including the resin composition of the present invention provided on the support.
[0248] For the resin composition layer, in addition to including the resin composition of the present invention, as long as the effect of the present invention is not greatly damaged, any material may also be included, for example, sheet-like reinforcing members such as glass cloth may be included. However, when the resin composition layer includes a sheet-like reinforcing member, there is a tendency that the thickness of the resin composition layer increases, so from the viewpoint of reducing the thickness, the resin composition layer preferably does not include a sheet-like reinforcing member, for example, the resin composition layer is only composed of the resin composition. It should be noted that the characteristics of the aforementioned cured product are the characteristics of the cured product obtained by curing the resin composition layer of the resin composition without a sheet-like reinforcing member.
[0249] From the viewpoint of thinning of printed wiring board and providing a cured product having excellent insulation property even if the cured product of the resin composition is a thin film, the thickness of the resin composition layer is preferably below 70 μm, preferably below 50 μm, more preferably below 45 μm, and further preferably below 40 μm. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be set to more than 1 μm, more than 1.5 μm, more than 2 μm, or more than 5 μm, etc.
[0250] Examples of the support include films formed of a plastic material, metal foil and release paper, and films formed of a plastic material and metal foil are preferred.
[0251] When a film formed of a plastic material is used as a support, the plastic material includes, for example, polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0252] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, and copper foil is preferred. As the copper foil, a foil formed of a single metal of copper can be used, or a foil formed of an alloy of copper and other metals (for example, tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) can be used. As a specific example of a polyethylene terephthalate film, "Lumirror R80" manufactured by Toray Industries, Inc. can be cited.
[0253] The surface of the support that contacts the resin composition layer may be subjected to matte treatment, corona treatment, or antistatic treatment.
[0254] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent for the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins can be cited. As an alkyd resin-based release agent, "AL-5" manufactured by Lintec can be cited. The support with a release layer can use a commercial product, for example, "SK-1", "AL-5", "AL-7" manufactured by Lintec, which is a PET film having a release layer with an alkyd resin-based release agent as the main component, "Lumirror T60" manufactured by Toray Industries, "Purex" manufactured by Teijin, "Unipeel" manufactured by UNITIKA, etc.
[0255] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0256] In one embodiment, the resin sheet may further include other layers as needed. As the other layers, for example, a protective film selected according to the support body and disposed on the surface of the resin composition layer that is not bonded to the support body (i.e., the surface on the opposite side of the support body) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, dust and the like can be prevented from being attached to the surface of the resin composition layer or from being damaged on the surface of the resin composition layer.
[0257] The resin sheet can be produced, for example, by preparing a resin varnish obtained by dissolving a resin composition in an organic solvent, applying the resin varnish on a support using a die coater or the like, and drying the varnish to form a resin composition layer.
[0258] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the organic solvent in the resin varnish. For example, when a resin varnish containing 30% to 60% by mass of an organic solvent is used, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 to 10 minutes.
[0259] The resin sheet can be stored by winding it into a roll. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0260] [Printed wiring board]
[0261] The printed wiring board of the present invention comprises an insulating layer formed by a cured product of the resin composition of the present invention. The printed wiring board may be a flexible substrate or a rigid substrate. The cured product of the resin composition of the present invention is flexible and is therefore suitable for use when the printed wiring board is a flexible substrate.
[0262] [Laminated sheet]
[0263] The resin composition or resin sheet of the present invention can be used to manufacture a laminated sheet. A laminated sheet refers to a sheet manufactured by laminating and curing a multilayer resin composition layer. The laminated sheet contains a multilayer insulating layer as a cured product of the resin composition layer. Usually, the number of resin composition layers laminated to manufacture a laminated sheet is consistent with the number of insulating layers contained in the laminated sheet. The number of specific insulating layers per laminated sheet is usually more than 2, preferably more than 3, particularly preferably more than 5, preferably less than 20, more preferably less than 15, and particularly preferably less than 10.
[0264] The laminated sheet is a sheet used by bending in a manner relative to one of its faces. The minimum bending radius of the bending of the laminated sheet is not particularly limited, preferably more than 0.1 mm, more preferably more than 0.2 mm, further preferably more than 0.3 mm, preferably less than 5 mm, more preferably less than 4 mm, and particularly preferably less than 3 mm.
[0265] Holes may be formed in each insulating layer included in the laminated sheet, and the holes can function as through holes or through holes in the multi-layer flexible substrate.
[0266] For the laminated sheet, in addition to the insulating layer, it can also further include any element. For example, the laminated sheet can have a conductor layer as an arbitrary element. The conductor layer can usually be partially formed on the surface of the insulating layer or between the insulating layers. The conductor layer usually functions as a wiring in the multilayer flexible substrate.
[0267] The conductor material used in the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor material may be a single metal or an alloy. As an alloy, for example, an alloy of two or more metals selected from the above group (for example, nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) can be cited. Among them, from the viewpoint of versatility, cost, ease of patterning, etc. of forming the conductor layer, chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper as a single metal is preferred; and alloys such as nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy. Among them, single metals of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper are better; and nickel-chromium alloy, and single metal of copper is further better.
[0268] The conductor layer may be a single layer structure or a multilayer structure including two or more single metal layers or alloy layers formed of different types of metals or alloys. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0269] The conductor layer may be patterned so as to function as wiring.
[0270] The thickness of the conductor layer depends on the design of the multi-layer flexible substrate, and is preferably 3 μm to 35 μm, more preferably 5 μm to 30 μm, further preferably 10 μm to 20 μm, particularly preferably 15 μm to 20 μm.
[0271] The thickness of the laminated sheet is preferably at least 100 μm, more preferably at least 150 μm, particularly preferably at least 200 μm, and is preferably at most 2000 μm, more preferably at most 1000 μm, particularly preferably at most 500 μm.
[0272] <Method for producing laminated sheet>
[0273] The laminated sheet can be manufactured using a manufacturing method including the following steps: (a) a step of preparing a resin sheet; and (b) a step of using the resin sheet and laminating and curing a plurality of resin composition layers. The order of laminating and curing the resin composition layers is arbitrary, as long as the desired laminated sheet can be obtained. Depending on the components contained in the resin composition, for example, after all the multi-layer resin composition layers are laminated, the laminated multi-layer resin composition layers can be cured together. In addition, for example, each time another resin composition layer is laminated on a certain resin composition layer, the laminated resin composition layer can be cured.
[0274] A preferred embodiment of step (b) is described below. In the embodiments described below, for the purpose of distinction, the resin composition layers are appropriately denoted with symbols in the form of "first resin composition layer" and "second resin composition layer", and further, the insulating layers obtained by curing these resin composition layers are also denoted with symbols in the form of "first insulating layer" and "second insulating layer" in the same manner as the resin composition layers.
[0275] In a preferred embodiment, step (b) comprises the following steps:
[0276] (II) a step of curing the first resin composition layer to form a first insulating layer;
[0277] (VI) a step of laminating a second resin composition layer on the first insulating layer; and
[0278] (VII) a step of curing the second resin composition layer to form a second insulating layer. In addition, step (b) may further include any of the following steps as required:
[0279] (I) a step of laminating a first resin composition layer on a sheet-like supporting substrate;
[0280] (III) a process of opening a hole in the first insulating layer;
[0281] (IV) a step of roughening the first insulating layer; and
[0282] (V) Step of forming a conductor layer on the first insulating layer Each step will be described below.
[0283] Step (I) is a step of laminating the first resin composition layer on the sheet-like supporting substrate before step (II). The sheet-like supporting substrate is a removable member, and for example, a plate-like, sheet-like, or film-like member can be used.
[0284] The lamination of the sheet-like support substrate and the first resin composition layer can be implemented by vacuum lamination. In the vacuum lamination, the heating and pressing temperature is preferably 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably implemented under reduced pressure conditions with a pressure of 26.7hPa or less.
[0285] Lamination can be performed by a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and an intermittent vacuum pressure laminator.
[0286] When using a resin sheet, the lamination of the sheet-like support substrate and the first resin composition layer can be performed by, for example, pressing the resin sheet from the support side, and heating and pressing the first resin composition layer of the resin sheet to the sheet-like support substrate. As a member (hereinafter sometimes appropriately referred to as "heating and pressing member") for heating and pressing the resin sheet to the sheet-like support substrate, for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It is better not to directly press the heating and pressing member to the resin sheet, but to press it across an elastic material such as heat-resistant rubber so that the first resin composition layer fully follows the surface unevenness of the sheet-like support substrate.
[0287] After lamination, the first resin composition layer can be smoothed by, for example, pressing with a heating and pressing member at normal pressure (atmospheric pressure). For example, when a resin sheet is used, the resin sheet is pressed with a heating and pressing member from the support side, so that the first resin composition layer of the resin sheet can be smoothed. The pressing conditions of the smoothing treatment can be set to the same conditions as the heating and pressing conditions of the above-mentioned lamination. The smoothing treatment can be carried out using a commercially available laminator. The lamination and smoothing treatment can be carried out continuously using the above-mentioned commercially available vacuum laminator.
[0288] Step (II) is a step of curing the first resin composition layer to form a first insulating layer. The curing conditions of the first resin composition layer are not particularly limited, and the conditions used when forming the insulating layer of the printed wiring board can be arbitrarily applied. For the first resin composition layer, if it is dried, it can be cured, but in the case of containing a thermosetting resin such as an epoxy resin, it can be cured by heat curing in addition to drying.
[0289] Generally, when epoxy resin is included, specific heat curing conditions vary depending on the type of resin composition. For example, the curing temperature is preferably 120°C to 240°C, more preferably 150°C to 220°C, and further preferably 170°C to 210°C. In addition, the curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 110 minutes, and further preferably 20 minutes to 100 minutes.
[0290] In the case of containing epoxy resin, before the first resin composition layer is thermally cured, the first resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the first resin composition layer is thermally cured, the first resin composition layer may be preheated at a temperature of 50°C or more and less than 120°C (preferably 60°C or more and 115°C or less, more preferably 70°C or more and 110°C or less) for more than 5 minutes (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes).
[0291] Step (III) is a step of drilling holes in the first insulating layer. Through this step (III), holes such as through holes and through holes can be formed in the first insulating layer. The drilling can be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition. The size and shape of the hole can be appropriately set according to the design of the multilayer flexible substrate.
[0292] Step (IV) is a step of roughening the first insulating layer. Usually, in step (IV), contamination (smear) is also removed. Therefore, the roughening treatment is sometimes referred to as desmear treatment. Examples of the roughening treatment include a swelling treatment using a swelling solution, a roughening treatment using an oxidant, and a neutralization treatment using a neutralizing solution.
[0293] The swelling liquid is not particularly limited, and examples thereof include alkaline aqueous solutions such as sodium hydroxide aqueous solution and potassium hydroxide aqueous solution. Examples of commercially available swelling liquids include "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid can be performed, for example, by immersing the cured body in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0294] As the oxidant, there is no particular limitation, and an alkaline permanganate solution formed by dissolving permanganate in a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution can be cited. The concentration of the permanganate in the alkaline permanganate solution is preferably 5 mass % to 10 mass %. As a commercially available oxidant, an alkaline permanganate solution such as "Concentrate Compact P", "Concentrate Compact CP", "Dosing Solution Securiganth P" made by Atotech Japan Co., Ltd. can be cited. The roughening treatment using the oxidant can be carried out by immersing the cured body in an oxidant solution heated to 60°C to 80°C for 10 minutes to 30 minutes.
[0295] In addition, an acidic aqueous solution can be used as a neutralizing solution. As a commercially available product, for example, "Reduction Solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited. The treatment with the neutralizing solution can be carried out by immersing the solidified body in a neutralizing solution at 30°C to 80°C for 5 minutes to 30 minutes. In consideration of operability, it is preferred to immerse the solidified body in a neutralizing solution at 40°C to 70°C for 5 minutes to 20 minutes.
[0296] The arithmetic mean roughness (Ra) of the surface of the roughened first insulating layer is preferably 400 nm or less, more preferably 300 nm or less, further preferably 200 nm or less. The lower limit is not particularly limited, and may be 30 nm or more, 40 nm or more, or 50 nm or more.
[0297] Step (V) is a step of forming a conductor layer on the first insulating layer as needed. Regarding the method for forming the conductor layer, for example, a plating method, a sputtering method, a vapor deposition method, etc. can be cited, among which a plating method is preferred. As a preferred example, a method of plating on the surface of the first insulating layer using an appropriate method such as a semi-additive method and a full-additive method to form a conductor layer having a desired wiring pattern can be cited. Among them, from the viewpoint of simplicity of manufacture, a semi-additive method is preferred.
[0298] The following is an example of forming a conductor layer using a semi-additive method. First, a plating seed layer is formed on the surface of a first insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer corresponding to a desired wiring pattern to expose a portion of the plating seed layer. A metal layer is formed on the exposed plating seed layer by electrolytic plating, and then the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, thereby forming a conductor layer having a desired wiring pattern.
[0299] In step (II), a first insulating layer is obtained, and step (III), step (IV), and step (V) are performed as needed, and then step (VI) is performed. Step (VI) is a step of laminating a second resin composition layer on the first insulating layer. The lamination of the first insulating layer and the second resin composition layer can be performed by the same method as the lamination of the sheet-like supporting substrate and the first resin composition layer in step (I).
[0300] However, when the first resin composition layer is formed using a resin sheet, the support of the resin sheet is removed before step (VI). The support may be removed between step (I) and step (II), between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V).
[0301] After step (VI), step (VII) is performed. Step (VII) is a step of curing the second resin composition layer to form a second insulating layer. The curing of the second resin composition layer can be performed by the same method as the curing of the first resin composition layer in step (II). Thus, a laminated sheet including a multilayer insulating layer such as a first insulating layer and a second insulating layer can be obtained.
[0302] In addition, in the method according to the aforementioned embodiment, as necessary, a step (VIII) of opening a hole on the second insulating layer, a step (IX) of roughening the second insulating layer, and a step (X) of forming a conductor layer on the second insulating layer may be performed. The opening of the second insulating layer in step (VIII) may be performed by the same method as the opening of the first insulating layer in step (III). In addition, the roughening of the second insulating layer in step (IX) may be performed by the same method as the roughening of the first insulating layer in step (IV). Furthermore, the formation of the conductor layer on the second insulating layer in step (X) may be performed by the same method as the formation of the conductor layer on the first insulating layer in step (V).
[0303] In the aforementioned embodiment, the embodiment of manufacturing a laminated sheet by stacking and curing of two layers of resin composition layers such as the first resin composition layer and the second resin composition layer is described, but a laminated sheet can also be manufactured by stacking and curing of more than three layers of resin composition layers. For example, in the method related to the aforementioned embodiment, the stacking and curing of the resin composition layer performed by steps (VI) to (VII), and the opening of the insulating layer performed by steps (VIII) to (X) as needed, the roughening treatment of the insulating layer, and the formation of the conductor layer on the insulating layer can be repeatedly implemented to manufacture a laminated sheet. Thus, a laminated sheet comprising more than three layers of insulating layers can be obtained.
[0304] Furthermore, the method according to the above-mentioned embodiment may further include any steps other than the above-mentioned steps. For example, when step (I) is performed, a step of removing the sheet-like supporting substrate may be performed.
[0305] <Flexible substrate>
[0306] The flexible substrate includes an insulating layer formed by a cured product of the resin composition of the present invention. When the flexible substrate includes the aforementioned laminated sheet, a multilayer flexible substrate can be formed. The flexible substrate includes not only an insulating layer or a laminated sheet, but also any component. As the arbitrary component, for example, electronic components, cover films, etc. can be cited.
[0307] The multilayer flexible substrate can be manufactured by a manufacturing method including a method for manufacturing the above-mentioned laminated sheet. Therefore, the multilayer flexible substrate can be manufactured by a manufacturing method including the following steps: (a) a step of preparing a resin sheet, and (b) a step of using the resin sheet and laminating and curing a plurality of resin composition layers.
[0308] The method for manufacturing a multilayer flexible substrate includes not only the aforementioned steps but also any other steps. For example, the method for manufacturing a multilayer flexible substrate having an electronic component may include the step of joining the electronic component to a laminated sheet. Regarding the joining conditions between the laminated sheet and the electronic component, any conditions may be adopted under which the terminal electrodes of the electronic component and the conductor layer as wiring provided on the laminated sheet can be connected to each other. In addition, for example, the method for manufacturing a multilayer flexible substrate having a cover film may include the step of laminating the laminated sheet with the cover film.
[0309] The above-mentioned flexible substrate can usually be used by being bent in a manner that one surface of the laminated sheet included in the flexible substrate faces each other. For example, the flexible substrate is accommodated in a housing of a semiconductor device in a state where it is bent and reduced in size. In addition, for example, in a semiconductor device having a bendable movable portion, the flexible substrate is provided in the movable portion.
[0310] [Semiconductor devices]
[0311] The semiconductor device includes the aforementioned printed wiring board. The semiconductor device includes, for example, a printed wiring board and a semiconductor chip mounted on the printed wiring board. In most semiconductor devices, the printed wiring board can be folded in a manner such that one surface of the printed wiring board faces the other and is accommodated in a housing of the semiconductor device. The printed wiring board may be the aforementioned flexible substrate or multilayer flexible substrate.
[0312] Examples of the semiconductor device include various semiconductor devices that can be used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and aircraft).
[0313] The semiconductor device described above can be manufactured, for example, by a manufacturing method including the steps of preparing a flexible substrate, bending the flexible substrate so that one surface thereof faces each other, and housing the bent flexible substrate in a housing.
[0314] Example
[0315] Hereinafter, the present invention will be specifically described by showing examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass" respectively unless otherwise expressly stated. In addition, the operations described below are performed under normal temperature and pressure unless otherwise expressly stated.
[0316] <Synthesis Example 1: Preparation of Varnish A Containing Bu Polymer a>
[0317] In a reaction container, 50.0 g of difunctional hydroxy-terminated polybutadiene "G-3000" (number average molecular weight: 5047 (GPC method), hydroxyl equivalent: 1798 g / eq., non-volatile component: 100 mass %) (hereinafter also referred to as "PBu material") manufactured by Nippon Soda Co., Ltd., 23.5 g of an aromatic hydrocarbon mixed solvent ("Ipzole (イプゾール) 150" manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin dilaurate were added and mixed to uniformly dissolve the components. As soon as it became uniform, the temperature was raised to 50°C, and 4.8 g of toluene-2,4-diisocyanate (isocyanate group equivalent: 87.08 g / eq.) (hereinafter also referred to as "TDI") was added while stirring, and the reaction was carried out for about 3 hours. Thus, a first reactant was obtained. Next, the first reactant was cooled to room temperature.
[0318] To the obtained first reactant, 8.96 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (anhydride equivalent: 161.1 g / eq.) (hereinafter also referred to as "BTDA"), 0.07 g of triethylenediamine, and 40.4 g of ethyl diglycol acetate (manufactured by Daicel Corporation) were added, and the mixture was heated to 130° C. with stirring to allow the reaction to proceed for about 4 hours.
[0319] FT-IR was used to analyze the 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered as the end point of the reaction, and the obtained second reactant was cooled to room temperature. In addition, the second reactant was filtered with a 100-mesh filter cloth to filter out solids. Thus, as a filtrate, a varnish containing Bu polymer a (hereinafter also referred to as "varnish A") was obtained.
[0320] Based on the above reaction process, it is inferred that the Bu polymer a is a polymer resin containing a PBu structure derived from a PBu material as a butadiene skeleton, having an urethane bond derived from the PBu material and TDI, having an imide structure derived from TDI and BTDA, and containing a divalent aromatic group derived from TDI and a trivalent aromatic group derived from BTDA.
[0321] The properties of Bu polymer a and varnish A are as follows;
[0322] Viscosity of varnish A: 7.5 Pa·s (25°C, E-type viscometer)
[0323] Content of non-volatile components (Bu polymer a) in varnish A: 50 mass%
[0324] Acid value of Bu polymer a: 16.9 mgKOH / g Number average molecular weight of Bu polymer a: 13723
[0325] Glass transition temperature of Bu polymer a: -10℃
[0326] Content ratio of butadiene skeleton in Bu polymer a: 78.4 mass%
[0327] Here, the content ratio (percentage) of the butadiene skeleton was calculated by the following formula using the mass parts of each material used:
[0328] {50.0 / (50.0+4.8+8.96)}×100.
[0329] <Synthesis Example 2: Preparation of Varnish B Containing Bu Polymer b>
[0330] In a reaction container, 69.0 g of a difunctional hydroxyl-terminated polybutadiene "G-3000" (number average molecular weight: 5047 (GPC method), hydroxyl equivalent: 1798 g / eq., non-volatile content: 100 mass%) ("PBu material") manufactured by Nippon Soda Co., Ltd., 40.0 g of an aromatic hydrocarbon mixed solvent ("Ipzole 150" manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were added and mixed to uniformly dissolve the components. Immediately after the mixture became uniform, the temperature was raised to 60° C., and 8.0 g of isophorone diisocyanate (manufactured by Evonik Degussa Japan Co., Ltd., isocyanate equivalent: 113 g / eq.) (hereinafter also referred to as "IPDI") was added while stirring, and the mixture was reacted for about 3 hours. Thus, a first reactant was obtained.
[0331] Next, 23.0 g of DIC cresol novolac resin "KA-1160" (hydroxyl equivalent: 117 g / eq.) (hereinafter also referred to as "PO skeleton material") and 60.0 g of diethylene glycol monoethyl ether acetate (produced by Daicel Chemical Industries, Ltd.) were added to the first reactant, and the mixture was heated to 150°C while stirring to carry out the reaction for about 10 hours.
[0332] FT-IR was used to analyze the 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered as the end point of the reaction, and the obtained second reactant was cooled to room temperature. In addition, the second reactant was filtered with a 100-mesh filter cloth to filter out solids. Thus, as a filtrate, a varnish containing Bu polymer b (hereinafter also referred to as "varnish B") was obtained.
[0333] From the above reaction process, it is inferred that the Bu polymer b is a polymer resin containing a PBu structure derived from a PBu material as a butadiene skeleton, having urethane bonds derived from a PBu material and IPDI and urethane bonds derived from IPDI and a PO skeleton material, and containing a cresol novolac skeleton containing a divalent aromatic group derived from a PO skeleton material and a phenolic hydroxyl group.
[0334] The properties of Bu polymer b and varnish B are as follows:
[0335] Content of non-volatile components (Bu polymer b) in varnish B: 50 mass %
[0336] Number average molecular weight of Bu polymer b: 5900
[0337] Glass transition temperature of Bu polymer b: -7°C
[0338] Content ratio of butadiene skeleton in Bu polymer b: 69.0 mass %
[0339] Here, the content ratio (percentage) of the butadiene skeleton was calculated by the following formula using the mass parts of each material used:
[0340] {69.0 / (69.0+8.0+23.0)}×100.
[0341] <Example 1>
[0342] [Preparation of resin composition E1]
[0343] 5 parts of a biphenylol epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 185) as the component (D-1), 5 parts of a naphthalene epoxy resin ("ESN475V" manufactured by Nippon Steel & Sumitomo Chemical Corporation, epoxy equivalent: about 332) as the component (D-1), 10 parts of a bisphenol AF epoxy resin ("YL7760" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 238) as the component (D-1), 2 parts of a cyclohexane epoxy resin ("ZX1658GS" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 135) as the component (D-1), 40 parts of a varnish A (non-volatile content: 50% by mass) as the component (A-1), and 10 parts of a cyclohexanone as a solvent were dissolved while heating and stirring to obtain a solution. The obtained solution was cooled to room temperature.
[0344] Then, to the obtained solution, 5 parts of an allyl group-containing benzoxazine compound "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd. as the component (C), 7.7 parts of an active ester curing agent ("EXB-8000L-65TM" manufactured by DIC Corporation, active group equivalent: about 220, 1:1 solution of toluene:MEK with 65% by mass of nonvolatile matter) as the component (D-2), and cresol novolac curing agent containing a triazine skeleton as the component (D-2) ("LA-3 018-50P", hydroxyl equivalent: about 151, 2-methoxypropanol solution with a solid content of 50%), 4 parts, an inorganic filler F as component (B) (100 parts of spherical silica "SC2500SQ" manufactured by Yaduma Co., Ltd., a surface-treated substance with 1 part of N-phenyl-3-aminopropyltrimethoxysilane ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.) (average particle size: 0.5 μm, specific surface area measured by the measurement method described below: 11.2 m 2 / g)), 35 parts of an amine curing accelerator (4-dimethylaminopyridine (DMAP)) as the component (E-1), and 0.03 parts of a peroxide curing accelerator ("PERBUTYL C" manufactured by NOF Corporation) as the component (E-2), the components were mixed and then uniformly dispersed using a high-speed rotary mixer. Thus, a dispersion was obtained.
[0345] The dispersion was then filtered with a cartridge filter ("SHP020" manufactured by ROKITECHNO) to remove solids of 2.0 μm or more. Thus, a resin composition E1 containing components (A), (B), (C), (D), and (E) was prepared as a filtrate.
[0346] [Preparation of Cured Material Film (A)]
[0347] A cured film (A) for evaluating moisture resistance was prepared as follows;
[0348] First, as a support, a polyethylene terephthalate film ("PET501010" manufactured by Lintec Corporation) having a release layer formed by subjecting one surface thereof to a release treatment was prepared.
[0349] Next, the resin composition E1 obtained in Example 1 was uniformly applied to the release layer of the support using a die coater so that the thickness of the resin composition layer after drying was 50 μm. The resin composition E1 was then dried at 80° C. to 110° C. (95° C. on average) for 6 minutes. Thus, a resin sheet (a) comprising a support and a resin composition layer comprising a resin composition disposed on the support was obtained.
[0350] Then, the resin composition layer of the resin sheet (a) was heat-treated at 200° C. for 90 minutes to cure. Then, the support was peeled off from the resin sheet. Thus, a cured film formed of a cured product of the resin composition was obtained (hereinafter, the cured film prepared in this way is also referred to as “cured film (A)”).
[0351] [Production of resin sheet (B)]
[0352] A resin sheet (B) for evaluating heat resistance was prepared as follows;
[0353] First, as a support, a polyethylene terephthalate film ("Lumirror R80" manufactured by Toray Industries, Ltd., thickness 38 μm, softening point 130° C.) having a release layer formed by performing a release treatment on one surface with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) was prepared.
[0354] Next, the resin composition E1 obtained in Example 1 is evenly coated on the release layer of the support using a die coater so that the thickness of the dried resin composition layer becomes 40 μm. Then, the resin composition E1 is dried at 70°C to 110°C for 5 minutes. Thus, a resin sheet comprising a support and a resin composition layer comprising a resin composition disposed on the support is obtained. Next, a rough surface of a polypropylene film ("ALPHAN MA-411" manufactured by Oji F-Tex Co., Ltd., thickness 15 μm) as a protective film is bonded to the surface of the resin composition layer that is not bonded to the support. Thus, a resin sheet having a support, a resin composition layer and a protective film in sequence is obtained (hereinafter, the resin sheet produced in this way will also be referred to as "resin sheet (B)"). Moreover, the obtained resin sheet (B) is provided for the evaluation of heat resistance described later.
[0355] [evaluate]
[0356] The produced cured product film (A) and resin sheet (B) were subjected to evaluation of moisture resistance and evaluation of heat resistance, respectively, which will be described later.
[0357] <Example 2>
[0358] In Example 1, 35 parts of the inorganic filler F as the component (B) was changed to 25 parts of the inorganic filler F;
[0359] Except for the above matters, the same operation as in Example 1 was carried out to prepare a resin composition E2 containing components (A), (B), (C), (D) and (E). In addition, the resin composition E2 was used instead of the resin composition E1, and the same operation as in Example 1 was carried out to prepare a cured film (A) and a resin sheet (B). The same operation as in Example 1 was carried out, and the prepared cured film (A) and resin sheet (B) were respectively subjected to the evaluation of moisture resistance and the evaluation of heat resistance.
[0360] <Example 3>
[0361] In Example 1, 40 parts of varnish A as component (A-1) was replaced with 40 parts of varnish B;
[0362] Except for the above matters, the same operation as in Example 1 was carried out to prepare a resin composition E3 containing components (A), (B), (C), (D) and (E). In addition, the resin composition E3 was used instead of the resin composition E1, and the same operation as in Example 1 was carried out to prepare a cured film (A) and a resin sheet (B). The same operation as in Example 1 was carried out, and the prepared cured film (A) and resin sheet (B) were respectively subjected to the evaluation of moisture resistance and the evaluation of heat resistance.
[0363] <Example 4>
[0364] In Example 1, 40 parts of varnish A as component (A-1) was replaced with 40 parts of "BX-360" manufactured by Nippon Kayaku Co., Ltd. (a toluene solution containing 50% by mass of non-volatile components; herein, "BX-360" is a butadiene skeleton-containing polymer containing a PBu structure as a butadiene skeleton and a p-PPE skeleton as a phenoxy structure);
[0365] Except for the above matters, the same operation as in Example 1 was carried out to prepare a resin composition E4 containing components (A), (B), (C), (D) and (E). In addition, the resin composition E4 was used instead of the resin composition E1, and the same operation as in Example 1 was carried out to prepare a cured film (A) and a resin sheet (B). The same operation as in Example 1 was carried out, and the prepared cured film (A) and resin sheet (B) were respectively subjected to the evaluation of moisture resistance and the evaluation of heat resistance.
[0366] <Comparative Example 1>
[0367] In Example 1, 5 parts of the allyl group-containing benzoxazine compound "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd. as the component (C) and 0.03 parts of the peroxide curing accelerator ("PERBUTYLC" manufactured by NOF Corporation) as the component (E-2) were not used. In addition, in Example 1, 35 parts of the inorganic filler F as the component (B) was changed to 32 parts of the inorganic filler F;
[0368] Except for the above matters, the same operation as in Example 1 was carried out to prepare a resin composition CE1 containing the components (A), (B), (D) and (E) (i.e., a resin composition not containing the component (C)). Furthermore, the resin composition CE1 was used instead of the resin composition E1, and the same operation as in Example 1 was carried out to prepare a cured film (A) and a resin sheet (B). The same operation as in Example 1 was carried out to evaluate the moisture resistance and the heat resistance, respectively.
[0369] <Comparative Example 2>
[0370] In Example 1, 5 parts of the allyl-containing benzoxazine compound "ALP-d" manufactured by Shikoku Chemical Industries, Ltd. as the component (C) was replaced with 5 parts of the allyl-free benzoxazine compound "Pd" manufactured by Shikoku Chemical Industries, Ltd. as the component (C'). In addition, in Example 1, 0.03 parts of the peroxide-based curing accelerator ("PERBUTYL C" manufactured by NOF Corporation) as the component (E-2) was not used;
[0371] Except for the above matters, the same operation as in Example 1 was carried out to prepare a resin composition CE2 containing the components (A), (C'), (D) and (E) (i.e., a resin composition containing the component (C') instead of the component (C)). Furthermore, the resin composition CE2 was used instead of the resin composition E1, and the same operation as in Example 1 was carried out to prepare a cured film (A) and a resin sheet (B). The same operation as in Example 1 was carried out to evaluate the moisture resistance and the heat resistance, respectively.
[0372] [Evaluation method and measurement method]
[0373] The measurement method and the evaluation method are shown below.
[0374] <Measurement of specific surface area>
[0375] The specific surface area of the inorganic filler F used in the above-mentioned Examples and Comparative Examples was measured as follows.
[0376] The specific surface area of the inorganic filler F was measured by adsorbing nitrogen gas on the surface of the inorganic filler F using a BET fully automatic specific surface area measuring apparatus ("Macsorb HM-1210" manufactured by Mountech Corporation) and calculating the specific surface area using a BET multipoint method.
[0377] <Evaluation of moisture resistance>
[0378] Using the cured film (A) obtained in the examples and comparative examples, moisture resistance was evaluated as follows: In brief, water absorption was measured and the value of water absorption was evaluated.
[0379] (Determination of water absorption)
[0380] First, the cured film (A) prepared in the example and the comparative example was cut into 40 mm squares to prepare a plurality of test pieces.
[0381] Next, one test piece according to Example 1 was dried at 130° C. for 30 minutes and then weighed to obtain a first weighing result. The first measured value obtained from the weighing result (i.e., the mass of the test piece before moisture absorption) was set as W. 0 (g). In addition, each test piece was placed in a constant temperature and humidity chamber (manufactured by ETAC) and after 96 hours at 60°C and 60% humidity, it was taken out of the constant temperature and humidity chamber and a second weighing result was obtained immediately after it was taken out. The second measured value (mass of the test piece after moisture absorption) obtained from the weighing result was set as W. 1 (g).
[0382] Then, the water absorption W of the test piece was calculated according to the following formula: A :
[0383] W A (%) = {(W 1 -W 0 ) / W 0}×100.
[0384] Similarly, for the other four test pieces involved in Example 1, the first weighing result and the second weighing result were obtained, and the water absorption W was calculated. A Then, the water absorption W of a total of 5 test pieces involved in Example 1 was calculated. A For other embodiments and comparative examples, the water absorption W of a total of 5 test pieces was calculated in the same manner. A The average value of .
[0385] (Evaluation Criteria)
[0386] Then, the water absorption W was evaluated as follows: A The average value of:
[0387] “○”: Water absorption rate WA The average value is less than 0.2%, showing excellent moisture resistance;
[0388] “×”: Water absorption rate W A The average value was 0.2% or more, indicating poor moisture resistance.
[0389] <Evaluation of heat resistance>
[0390] Using the resin sheets (B) obtained in the examples and comparative examples, heat resistance was evaluated as follows. In brief, an evaluation substrate (C) was prepared, and the evaluation substrate (C) was exposed to high temperature according to a reflow temperature profile that can be used when manufacturing a printed wiring board, and whether peeling occurred on the evaluation substrate (C) obtained thereafter was evaluated as a heat resistance test.
[0391] [Preparation of Evaluation Substrate (C)]
[0392] (1) Preparation of copper-clad laminate
[0393] First, as a copper-clad laminate, a glass cloth-based epoxy resin double-sided copper-clad laminate with copper foil layers laminated on both sides was prepared (copper foil thickness 3 μm, substrate thickness 0.15 mm, "HL832NSF LCA" manufactured by Mitsubishi Gas Chemical Co., Ltd., size 255×340 mm).
[0394] (2) Lamination of resin sheet (B)
[0395] The protective film is peeled off from each resin sheet (B) made in the embodiments and comparative examples to expose the resin composition layer. Next, an intermittent vacuum pressurized laminator (Nikko-Materials' 2-stage build-up laminator "CVP700") is used to laminate the resin sheet (B) with the protective film peeled off on both sides of the copper-clad laminate in such a way that the resin composition layer is in contact with the copper-clad laminate. Lamination is implemented in the following manner: after reducing the pressure for 30 seconds to adjust the air pressure to less than 13hPa, press bonding is performed at 130°C and a pressure of 0.74MPa for 45 seconds. Next, hot pressing is performed at 120°C and a pressure of 0.5MPa for 75 seconds.
[0396] (3) Thermal curing of resin composition layer
[0397] The copper-clad laminate with a resin sheet (B) laminated on both sides is put into a first oven and continuously exposed to a temperature of 100°C for 30 minutes. Then, it is switched to a second oven and continuously exposed to a temperature of 180°C for 30 minutes, thereby thermally curing the resin composition layer of the resin sheet (B) to form an insulating layer. Then, the copper-clad laminate with an insulating layer formed on both sides is taken out from the second oven. Then, the support is peeled off from the resin sheet (B) to expose the resin composition layer. Thus, a copper-clad laminate with an insulating layer exposed on both sides (hereinafter also referred to as "cured substrate (c1)") can be obtained.
[0398] (4) Roughening process
[0399] The cured substrate (c1) was subjected to a desmearing treatment as a roughening treatment. In addition, as the desmearing treatment, the following wet desmearing treatment was performed.
[0400] Wet decontamination treatment:
[0401] The cured substrate c1 is first immersed in a swelling solution ("Swelling Dip Securiganth P" manufactured by Atotech Japan, an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, then immersed in an oxidant solution ("Concentrate Compact CP" manufactured by Atotech Japan, an aqueous solution of potassium permanganate concentration of about 6% and sodium hydroxide concentration of about 4%) at 80°C for 20 minutes, and finally immersed in a neutralizing solution ("Reduction Solution Securiganth P" manufactured by Atotech Japan, an aqueous solution of sulfuric acid) at 40°C for 5 minutes. Then, the cured substrate c1 is taken out from the neutralizing solution and dried at 80°C for 15 minutes. In this way, a copper-clad laminate having a roughened surface of the insulating layer (hereinafter also referred to as "roughened substrate (c2)") can be obtained.
[0402] (5) Step of forming a conductor layer
[0403] [Preparation in Advance]
[0404] First, as preliminary preparation for forming a conductive layer on the surface of the roughened substrate (c2), the following steps (5-1) to (5-5) are sequentially performed.
[0405] (5-1) Alkaline cleaning (cleaning and charge adjustment of the insulating layer surface)
[0406] The surface of the roughened substrate (c2) was cleaned at 60°C for 5 minutes using a cleaning liquid (trade name "Cleaning Cleaner Securiganth 902" manufactured by Atotech Japan Co., Ltd.).
[0407] (5-2) Soft etching (cleaning)
[0408] The surface of the roughened substrate (c2) was treated with a sulfuric acid-acidic sodium persulfate aqueous solution at 30°C for 1 minute.
[0409] (5-3) Prepreg (charge adjustment on the surface of the insulating layer before adding Pd)
[0410] The surface of the roughened substrate (c2) was treated at room temperature for 1 minute using a chemical solution (trade name "Pre.Dip Neoganth B" manufactured by Atotech Japan Co., Ltd.) to adjust the charge on the surface of the insulating layer.
[0411] (5-4) Activator provision (providing Pd to the surface of the insulating layer)
[0412] The surface of the roughened substrate (c2) was treated at 35°C for 5 minutes using a chemical solution (trade name "Activator Neoganth 834" manufactured by Atotech Japan Co., Ltd.). Thus, Pd was provided on the surface of the insulating layer.
[0413] (5-5) Reduction (reduction of Pd provided to the insulating layer)
[0414] The surface of the roughened substrate (c2) was treated at 30°C for 5 minutes using a mixed solution (a mixed solution of "Reducer Neoganth WA" and "Reducer Acceralator 810mod." manufactured by Atotech Japan). Thus, the Pd applied to the surface of the insulating layer was reduced. As described above, the preliminary preparation for forming a conductor layer on the surface of the roughened substrate (c2) was completed.
[0415] [Electroless copper plating step (Cu is deposited on the surface of the insulating layer (Pd surface))]
[0416] Next, the surface of the roughened substrate (c2) was treated at 35°C for 15 minutes using a mixed solution (a mixed solution of "Basic Solution Printganth MSK-DK", "Copper Solution Printganth MSK (trade name)", "Stabilizer Printganth MSK-DK", and "Reducer Cu" manufactured by Atotech Japan Co., Ltd.). Thus, Cu was precipitated on the surface of the insulating layer (Pd surface) to form a first copper plating layer (hereinafter also referred to as "electroless copper plating layer"). The thickness of the formed electroless copper plating layer was 1 μm.
[0417] [Electrolytic copper plating step (forming a copper plating layer on the surface of the electroless copper plating layer)]
[0418] Then, on the roughened substrate (c2) formed with the electroless copper plating layer, electrolytic copper plating is performed to further form a second copper plating layer (hereinafter also referred to as "electrolytic copper plating layer") on the surface of the electroless copper plating layer. Thus, a conductor layer formed by the electroless copper plating layer and the electrolytic copper plating layer is formed. The thickness of the conductor layer (that is, the total thickness of the electroless copper plating layer and the electrolytic copper plating layer) is about 15 μm. In this way, a substrate with a conductor layer (hereinafter also referred to as "evaluation substrate (C)") is obtained.
[0419] (Heat resistance test)
[0420] The evaluation substrate (C) is cut into test pieces of 100 mm × 100 mm. The obtained test pieces are subjected to a heat resistance test. Specifically, the test pieces are placed in a reflow soldering device ("HAS6116" manufactured by ANTOM), and the test pieces are continuously subjected to a reflow soldering process based on the reflow soldering temperature curve (peak temperature: 260°C) for lead-free assembly based on IPC / JEDEC J-STD-020C ("Moisture / Reflow Sensitivity Classification For Nonhermetic Solid State Surface Mount Devices", July 2004) without being taken out of the reflow soldering device for 20 times, thereby simulating a heat resistance test.
[0421] (observe)
[0422] Furthermore, the surface of the test piece taken out from the reflow apparatus after the heat resistance test was visually observed to confirm whether there was peeling between the insulating layer and the conductive layer. If there was peeling, the number of the peeled portions was counted.
[0423] The observation results were evaluated according to the following evaluation criteria:
[0424] (Evaluation Criteria)
[0425] “○”: There are 2 or fewer peelings between the insulating layer and the conductor layer, indicating excellent heat resistance;
[0426] "×": There were 3 or more places where the insulating layer and the conductive layer were peeled off, indicating poor heat resistance.
[0427] [result]
[0428] The results of the above examples and comparative examples are shown in Table 1. In Table 1, the amount of each component represents the amount of non-volatile components. The content of the component (A), the content of the component (B), and the content of the component (C) in Table 1 represent the percentages [mass %] when the non-volatile components in the resin composition are set to 100 mass %.
[0429] [Table 1]
[0430]
[0431] <Discussion>
[0432] As can be seen from Table 1, by comparing the examples with the comparative examples, it can be seen that in the examples, a resin composition capable of obtaining a cured product having excellent heat resistance and moisture resistance can be provided. In addition, it can be seen that: a cured product of the resin composition involved in the examples; a resin sheet comprising the resin composition; a printed wiring board comprising an insulating layer formed using the cured product of the resin composition, and a semiconductor device comprising the printed wiring board can also be provided.
[0433] In addition, the evaluation substrates (C) involved in Examples 1 to 4 were bent, and as a result, no cracks were confirmed in the bent portion. Therefore, it can be seen that a resin composition that can produce a cured product with excellent flexibility can be provided. In addition, it can be seen that: a cured product of the resin composition involved in the embodiment; a resin sheet containing the resin composition; a flexible substrate containing an insulating layer formed using the cured product of the resin composition, and a semiconductor device containing the flexible substrate can also be provided.
[0434] It should be noted that in Examples 1 to 4, even when one or both of the components (D) and (E) are not contained, the same results as those of the above-described Examples are obtained, although the degree of difference exists. In addition, in Examples 1 to 4, even when the component (C') is contained in an amount that does not significantly hinder the desired effect of the present invention, the same results as those of the above-described Examples are obtained, although the degree of difference exists.
Claims
1. A resin composition comprising the following components (A) to (D), (A) a polymer containing a butadiene skeleton, (B) Inorganic filling materials, (C) a benzoxazine compound containing a substituted or unsubstituted allyl group, and (D) thermosetting resin, in, (D) The thermosetting resin includes an epoxy resin and (D-2) a resin that functions as a curing agent, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (A) is 0.1 mass % or more and 50 mass % or less, When the nonvolatile component in the resin composition is 100 mass %, the content of the (B) inorganic filler is 60 mass % or less and greater than 0 mass %, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (C) is 0.01 mass % or more and 30 mass % or less, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (D) is 5.1 mass % or more and 80 mass % or less, When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (D-2) is 0.1 mass % or more and 30 mass % or less.
2. The resin composition according to claim 1, wherein The component (A) is a butadiene skeleton-containing polymer having one or two or more aromatic groups in the molecule.
3. The resin composition according to claim 2, wherein At least one of the aromatic groups forms part of the phenoxy structure.
4. The resin composition according to claim 3, wherein The phenoxy structure includes a phenoxy structure represented by the following formula (A2-2): In the above formula (A2-2), A a1 ~A a6 Two of them are chemical bonds, and the remaining four are each independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted straight-chain alkyl group having 1 to 5 carbon atoms; wherein A a1 In the case of non-chemical bonds, it is a hydrogen atom.
5. The resin composition according to claim 4, wherein In formula (A2-2), A a1 is a hydrogen atom, and in the A that is not a chemical bond a2 ~A a6 At least one of them is a methyl group.
6. The resin composition according to claim 4, wherein In formula (A2-2), A a1 is a chemical bond, and in A which is not a chemical bond a2 ~A a6 At least one of them is a methyl group.
7. The resin composition according to claim 3, wherein The phenoxy structure includes a phenoxy structure represented by the following formula (A2-3), In the above formula (A2-3), A b1 and A b2 is a chemical bond, A b3 ~A b6 Each is independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted linear alkyl group having 1 to 5 carbon atoms.
8. The resin composition according to claim 7, wherein In formula (A2-3), in A b3 ~A b6 At least one of them is a methyl group.
9. The resin composition according to claim 2, wherein The component (A) is a butadiene skeleton-containing polymer in which one aromatic group exists between two butadiene skeletons.
10. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (A) is 15% by mass or more.
11. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (A) is 45% by mass or less.
12. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 60% by mass or less.
13. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (B) is less than 50 mass %.
14. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 45% by mass or less.
15. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 0.1% by mass or more.
16. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 10% by mass or more.
17. The resin composition according to claim 1, wherein The component (C) is a benzoxazine compound containing two or more benzoxazine structures in the molecule.
18. The resin composition according to claim 1, wherein The component (C) is a benzoxazine compound containing two or more allyl groups in the molecule.
19. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 0.02% by mass or more.
20. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 3% by mass or more.
21. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 10% by mass or less.
22. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (D) is 11% by mass or more.
23. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the component (D) is 55 mass % or less.
24. The resin composition according to claim 1, wherein It further contains (E) a curing accelerator.
25. The resin composition according to claim 24, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (E) is 0.001 mass % or more.
26. The resin composition according to claim 24, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (E) is 0.02% by mass or more.
27. The resin composition according to claim 24, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the component (E) is 2 mass % or less.
28. The resin composition according to claim 24, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the (E) component is 1 mass % or less.
29. The resin composition according to claim 1, wherein the water absorption of the cured product thereof is less than 0.2%.
30. The resin composition according to claim 1, wherein the water absorption of the cured product thereof is less than 0.19%.
31. The resin composition according to claim 1, which is used for forming an insulating layer.
32. A cured product, which is a cured product of the resin composition according to any one of claims 1 to 31.
33. A resin sheet comprising: Support body, and A resin composition layer provided on the support and comprising the resin composition according to any one of claims 1 to 31. 34 . A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to claim 1 .
35. A printed wiring board comprising an insulating layer formed from the cured product according to claim 32. 36 . A flexible substrate comprising an insulating layer formed from a cured product of the resin composition according to claim 1 .
37. A flexible substrate comprising an insulating layer formed from the cured product according to claim 32.
38. A semiconductor device comprising the printed wiring board according to claim 34. A semiconductor device comprising the flexible substrate according to claim 36 .
Citation Information
Patent Citations
Bismaleimide resin composition and use of the same
JP2016074871A
Halogen-free resin composite and use thereof
CN104845363A